Engineered lipase enables selective hydrolysis of palmitic over oleic acyl chains at a two‑phase microfluidic interface - Jin-Zheng Wang; Lu Tan; Cheng-Kun Wu; Xin-Ying Wang; Kheng Lim Goh; Richard Ansah Herman; Shuai You; Sheng Sheng; Fu-An Wu; Jun Wang (Bioresource Technology, 2026)

Late Miocene pollen record and quantitative paleoclimate and paleoelevation reconstructions for the Jianzha Basin, northeastern Tibetan Plateau - Beibei Zhang; Chaofeng Fu; Feng Wang; Fengyan Lu; Chen Liang; Cheng Quan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

A novel bidentate coordination bis-thionocarbamate collector for copper-sulfur separation under low-alkalinity conditions: Synthesis and adsorption mechanism - Zekun Wang; Xiaokun Fu; Yan Jin; Yao Meng; Haoran Cheng; Louyan Shen; Ming Li; Xingrong Zhang (Chemical Engineering Journal, 2026)

Fate of antibiotic resistance genes during rural domestic wastewater treatment: Anaerobic unit as enrichment hotspot versus aerobic unit as attenuation zone - Bingbing Feng; Juan Chen; Chao Wang; Jingjing Fu; Rong Wang; Jingjing Zhang; Bo Zhang; Cheng Cheng (Bioresource Technology, 2026)

Reshaping of extracellular polymeric substance scaffolds, microbiota and metabolism mitigates bio-clogging in microbial fuel cell-coupled constructed wetlands - Qinghua Wang; Jiao Yin; Xuewei Fu; Lei Cheng; Xinyue Wu; Xiaofang Li; Haowei Guo; Jun Xiao; Lei Huang (Bioresource Technology, 2026)

Addressing the protein challenge in aquaculture: Nutritional attributes, application bottlenecks and refinement strategies for single-cell protein - Jiayv Zhang; Shanfei Fu; Rui Li; Mengxue Li; Zhenni Cheng; Xiaolei Fan; Rongbo Guo; Haiqing Wang (Animal Feed Science and Technology, 2026)

Phthalate esters and microplastics in sediments of Haomeiliao Wetland, Southwestern Taiwan: Occurrence, spatial distribution, and management implications - Aila Marie Bandola; Ming-Huang Wang; Bo-Fu Guo; Kristopher Ray S. Pamintuan; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Predicting citywide human mobility with a graph-prior-enhanced euclidean convolutional network - Sheng Wu; Linbaizhi Wang; Peixiao Wang; Hengcai Zhang; Shifen Cheng; Xin Fu; Junhao Guo; Feng Lu (Sustainable Cities and Society, 2026)

Middle Jurassic isolated dinosaur tracks from Msemrir (Central High Atlas, Morocco): Evidence for theropod occurrence and paleogeographic distribution - Noura Lkebir; Yao-Yan He; Xiong-Wei Zeng; Cheng-Gang Wang; Fa-Fu Wu; Lai-Shi Zhao; Zhi-Jun Niu (Palaeoworld, 2026)

Recent intensification of the negative physiological effect of CO2 on terrestrial evaporation - Haiyang Qian; Weiguang Wang; Zefeng Chen; Akash Koppa; Guoshuai Liu; Jian Zeng; Jianyu Fu; Shuai Cheng; Diego G. Miralles (Journal of Hydrology, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

The boosted light utilization and spatial charge separation efficiency of ZnIn2S4 photoanode for photoelectrochemical hydrogen evolution by synergistical action of non-metal plasmonic effect and charge transport channel - Kangwei Zhang; Guozhong Wei; Bufan Liu; Hongyu Wang; Ruoyi Jin; Lang Cheng; Ziyi Wang; Zhen Qu; Junli Fu; Guling Zhang; Wenzhong Wang (Journal of Environmental Chemical Engineering, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

Climate-induced forest destabilization and shrub stabilization in Africa - Linhai Cheng; Qiang Tang; Nan Lu; Yafeng Wang; Changjia Li; Shuai Wang; Xiangyi Li; Phuping Sucharitakul; Yongzhe Chen; Zhihong Xu; Lindsay C. Stringer; Bojie Fu (Global and Planetary Change, 2026)

Effects of different drying methods on drying characteristics and quality of chili peppers (Capsicum annuum L.): Insights from changes in carotenoid and alkaloid secondary metabolites - Xuanxuan Yang; Xuefang Li; Fu Cai; Gang Shen; Cheng Zhang; Jun Wang (Food Research International, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Traceable method for differential code bias estimation in PPP one-way timing - Fu Zheng; Conghan Wang; Xiaopeng Gong; Cheng Yang; Dong Zhang; Yu Xue; Ran Yao; Yuzhuo Wang; Chuang Shi (GPS Solutions, 2026)

A synergy strategy of deep eutectic solvents and boric acid modified β-CD polymer for enhancing enantioseparation in HPLC - Xiaoqian Yuan; Ziyi Cheng; Jiajia Fu; Wanting Duan; Yuchen Cui; Ruijun Tang; Xinru Wang; Youxin Li (Analytica Chimica Acta, 2026)

Strigolactones constrain rice drought acclimation by suppressing ROS scavenging through the D53–OsWRKY31–ZFP36 module - Qianqian Li; Yi Wang; Jijun Yan; Liquan Kou; Hao Zhang; Jinhua Yang; Qingliang Hu; Yanshuo Guo; Xinwei Ban; Nan Luo; Peiyong Xin; Yanhui Jing; et al. (Molecular Plant, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Oral exposure to non-brain-penetrable microplastics induces neurotoxicity via disrupting the gut microbiota−tryptophan metabolism−microglial autophagy cascade - Yulong Wu; Zhouyan Dong; Dong Wang; Jiayi Dong; Xinze Jiang; Guangcheng Fu; Mei Cheng (Journal of Hazardous Materials, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Pectin film reinforced with self-assembled lignin/bayberry bark tannin nanoparticles for preserving perishable fruits - Haonan Guo; Yijing Li; Xinxin Cheng; Quanbin Fu; Jin Wang; Bowen Zhang; Shikai Zhang; Houshen Li (Food Hydrocolloids, 2026)

Persistently high oxidative burden of PM2.5 amidst declining mass concentration: Evidence from long-term observation in Shanghai - Yue Huang; Yuankai Xie; Wei Zhang; Lu Xu; Ming Hu; Cheng Huang; Qingyan Fu; Steven J. Campbell; Gang I. Chen; David C. Green; Jialiang Feng; Shunyao Wang (Environmental Pollution, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Ultrahigh energy storage in BNBT-ST ceramics enabled by multiscale heterogeneous structures - Zhifei Zhang; Juntao Huang; Yuxin Xu; Saifei Wang; Guangyao Li; Chengchao Hu; Haihua Huang; Jigong Hao; Wei Li; Zhenxiang Cheng; Mahesh Kumar Joshi; Peng Fu (Chemical Engineering Journal, 2026)

Coordination-driven self-assembly of cerium-baicalein nanozyme promotes spinal cord injury repairing by simultaneously scavenging mitochondrial ROS and reprogramming macrophage polarization - Zhefan Xie; Cheng Peng; Xiaofeng Li; Yuqi Zhao; Shenghang Liu; Xuenian Ye; Yuxue Wang; Wenchong Tan; Huimin Hu; Jianqiang Li; Yanming Ma; Chunlai Fu (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Source Transition and Health Implication of PM2.5-Bound Metals: Multi-year High-resolution Observation in a Coastal Megacity - Yanjie Lei; Ming Hu; Yuankai Xie; Anja H. Tremper; Yue Liu; Lan Hong; Xin Cheng; Cheng Huang; Qingyan Fu; Jialiang Feng; David C. Green; Longhua Wu; et al. (Atmospheric Environment, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

Microbiota-derived 4-HPAA alleviates Crohn’s disease by stabilizing SIRT1 and reprogramming macrophage immunometabolism - Chao Cheng; Shaoqi Cheng; Wenliang Jiang; Shuqiang Fu; Yangjie Shang; Xiufang Tang; Jie Zhao; Honggang Wang (Apoptosis, 2026)

Expression and Functional Characterisation of EhSWP 26 in Ecytonucleospora hepatopenaei : Insights From RNA Interference and Subcellular Localisation Analyses - Huiwen Jiang; Xiaohui Cao; Yi Qiao; Tingyue Liu; Jie Cheng; Ge Jiang; Xianping Fan; Haibo Wang; Kuipeng Fu; Hui Shen (Journal of Fish Diseases, 2026)
Ecytonucleospora hepatopenaei (EHP) is an obligate intracellular microsporidian that causes severe growth retardation in Penaeus vannamei (P. vannamei ), yet its pathogenic mechanisms remain incompletely clear. As the spore wall is essential for resisting environmental stress and mediating host invasion, characterising its protein components is critical for elucidating EHP biology. In this study, we identified and cloned a novel spore wall protein, EhSWP26. Sequence analysis revealed that EhSWP26 contains a 687 bp open reading frame encoding a 228‐amino‐acid polypeptide, lacking a signal peptide and transmembrane domain but harbouring a conserved MICSWaP (Microsporidia Spore Wall and Associated Proteins) domain characteristic of the microsporidian MICSWaPs family. Immunoelectron microscopy and indirect immunofluorescence assays demonstrated that EhSWP26 localises to the mature spore wall, where it is distributed in both the exospore and endospore layers. RNA interference further confirmed that silencing EhSWP26 significantly reduced its transcript level and led to a marked decrease in EHP spore load in shrimp hepatopancreas. Collectively, these findings indicate that EhSWP26 is a key structural and functional component associated with spore wall formation and host infection, likely playing an essential role in the EHP life cycle. This study enhances our understanding of EHP spore wall composition and function, provides a foundation for investigating its proliferation and infection mechanisms, and highlights EhSWP26 as a promising target for diagnostic development and therapeutic intervention in EHP disease of P. vannamei .

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Anti-collision design and oblique collision analysis of ECC strengthened RC piers with a steel-GFRP-foam fender protection - Yi Cheng; Fei Wang; Wen-Wei Wang; Tianhao Han; Yuan Yue; Jiahui Fu; Yongming Xiong (Ocean Engineering, 2026)

Late Triassic tectonic evolution and regional climate response in the northern Tibetan Plateau: Insights into the Triassic–Jurassic mass extinction - Ruiyang Chai; Yanan Zhou; Teng Wang; Qiang Fu; Xiaohua Teng; XiaoJing Yang; Nan Jiang; Qinglong Chen; Zhenwei Chen; Ziwei Bian; Xin Cheng; Jingong Zhang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Geostatistical prior constrained Bayesian full-waveform inversion based on wasserstein-2 distance likelihood function - Wenze Cheng; Hanming Chen; Lingqian Wang; Yuxin Fu; Chi Fang; Hui Zhou (Journal of Applied Geophysics, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

Preferentially selective lithium recovery from spent lithium-ion battery leachates using NaBPh4/TBP synergistic extraction - Qian Cheng; Yue Wang; Yongxiang Wang; Panfeng Gao; Jun-Tao Li; Jiangxue Long; Haiyan Fu (Hydrometallurgy, 2026)

Quantitative criteria and deformation-dependent model for passive soil arching in compacted clay - Xiao-Hu Zhang; Han-Lin Wang; Xiang-Shen Fu; Cheng-Shuang Yin; Meng-Cheng Long (Computers and Geotechnics, 2026)

Genome-wide identification of the WOX gene family in Capsicum baccatum and the roles of CbWOX7 and CbWOX9 in promoting callus proliferation - Yu Zhang; Muhammad Imran; Huangying Shu; Liping Zhang; Huazheng Shao; Yingsai Li; Xu Lu; Shanhan Cheng; Huizhen Fu; Zhiwei Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Synthesis of Fluorescent Probe with D-π-A Structure and its Application in Dual-channel Recognition of Fe3+ - Junli Shi; Chenwei Fu; Shengling Li; Guo Cheng; Shijia Lei; Qian Wang; Yihuan Cao; Ziyu Zhang; Duanlin Cao (Journal of Fluorescence, 2026)

Mechanism Analysis and Precise Regulation Strategies of Non-Thermal Effects and Synergistic Effects in Microwave Disinfection - Ying-Xiang Fu; Jun-Jie Wang; Hao Wu; Zhi-Cheng Pan; Wei Hu; Ye Du (Current Pollution Reports, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Characterization of wheat starch–safflower seed oil complex and its effects on noodle quality and starch digestibility - Xiaochun Zheng; Xiaoxiao Liu; Jing Wang; Yini Fu; Meina Cheng; Li Tai; Xinwen Xu; Laizhong Wang; Yi Zhao; Min Liu; Wenyu Liu; Changqing Wei (Food Chemistry, 2026)

Transglutaminase-induced crosslinking of soy protein isolate in crowded environments: effects of dextran concentration and molecular weight - Kaiyun Luo; Siqi Fu; Yunhao Xing; Xiaohong He; Maolong Chen; Zhou Xu; Ye Jiao; Yunhui Cheng; Xufeng Wang (Food Chemistry, 2026)

Synthesis of N, S-co-doped carbon quantum dots derived from coralline algae polysaccharide and their application for grape preservation in gelatin films - Libo Wang; Xuan Fu; Kerou Gao; Yuhan Song; Hongda Zhang; Yanhui Wei; Kun Cheng (Food Bioscience, 2026)

Enhanced mechanical, thermal, and rheological properties of nanocellulose-reinforced multifunctional sanxan gum hydrogels - Yue Wang; Baoping Wang; Ping Cheng; Xue Zhang; Jun Han; Fang Tian; Lina Fu; Zhiping Fan (Food and Bioproducts Processing, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

A secreted alpha-amylase effectively induces reproductive cyst formation both within and across Colpoda species, key soil-dwelling protists - Zixin Cheng; Zhongqiao Song; Kejia Fu; Yuan Wang; Kai Chen; Jing Zhang; Che Hu; Xiaocui Chai; Shuai Luo; Fang Zhou; Yuan Xiao; Zhenfei Xing; et al. (Science China Life Sciences, 2026)

Transcription factors in phosphorus utilization: enhancing crop productivity and stress resilience - Manli Zhao; Yan Sun; Chenxi Fu; Siji Wang; Jianbo Shen; Sanyuan Tang; Lingyun Cheng (Planta, 2026)

Brown Algal Fermentation Products Improve Phosphorus Availability and Maize Growth in Low Phosphorus Soil - Siji Wang; Zikai Xu; Yan Sun; Manli Zhao; Chenxi Fu; Shuping Li; Lingyun Cheng (Journal of Plant Growth Regulation, 2026)

Correction: The Dynamics of Soil Organic Carbon in Alpine Grasslands Affected by Livestock Grazing Intensity - Jianghao Cheng; Gang Fu; Tao Ma; Zhaoqi Wang; Junxi Wu; Mingxue Xiang (Environmental Management, 2026)

Visualization on deformation characteristics of passive soil arching effect in unsaturated compacted clay under plane-strain condition - Xiao-Hu Zhang; Han-Lin Wang; Meng-Cheng Long; Zhen-Nan Tian; Xiang-Shen Fu; Cheng-Shuang Yin (Bulletin of Engineering Geology and the Environment, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A chemical cocktail rejuvenates senescent human mesenchymal stem cells and facilitates functional skin repair - Jiangbing Xiang; Yan Li; Huating Chen; Shuaifei Ji; Shaowen Cheng; Mengyang Wang; Yingying Li; Xiaobing Fu; Xiaoyan Sun; Yufeng Jiang (Science Bulletin, 2026)

Seasonal variation patterns and drivers of baseflow recession dynamics across Australia - Tianmei Wang; Lei Cheng; Xuxin Lei; Yunfan Zhang; Shujie Cheng; Chenhao Fu; Yao Lai; Lu Zhang (Journal of Hydrology, 2026)

A nonlinear quantitative analysis framework for investigating detrital zircon U Pb geochronological data - Yeqin Liu; Wenlei Wang; Qiuming Cheng; Yong Fu (Journal of Geochemical Exploration, 2026)

Three-dimensional ordered mesoporous Co1Mn2Ox composite oxides for highly efficient toluene oxidation: Achieving an optimal balance of adsorption, oxidation, and desorption - Xiaodan Wang; Wenbo Si; Qinyue Wang; Zhenchuan Hu; Cheng Li; Chunrong Xiong; Bingqing Zhang; Xiaoqian Fu; Xiaolei Hu (Journal of Environmental Chemical Engineering, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Dynamic cultivar-soil interactions drive accelerating genetic gains in a dryland wheat system - Yuan Li; Yong-He Zhu; He-Peng Lu; Neng Wang; Fu-Ying Cheng; Yan-Lei Du; Feng-Min Li (Field Crops Research, 2026)

Strigolactone-mediated regulation of chromium uptake, redox homeostasis, and photosynthetic carbon metabolism during Cr (VI) stress tolerance in Capsicum annuum L. - Kaiser Iqbal Wani; Huazheng Shao; Yingsai Li; Muhammad Aamir Manzoor; Huizhen Fu; Xu Lu; Shanhan Cheng; Javaria Tabusam; Tariq Aftab; Zhiwei Wang (Plant Cell Reports, 2026)

GABAergic Inhibition from the Nucleus Tractus Solitarius to Ventrolateral Medulla Phox2b Neurons Modulates Central Respiratory Chemoreflex and Ventilatory Homeostasis - Liuqi Shao; Yake Ji; Hongxiao Yu; Zixuan Cheng; Fanrao Kong; Xiaoyi Wang; Bingwen Zhang; Yinchang Wang; Yimeng Song; Fang Yuan; Congrui Fu; Sheng Wang (Neuroscience Bulletin, 2026)

The Dynamics of Soil Organic Carbon in Alpine Grasslands Affected by Livestock Grazing Intensity - Jianghao Cheng; Gang Fu; Tao Ma; Zhaoqi Wang; Junxi Wu; Mingxue Xiang (Environmental Management, 2026)

Iron plaque crystallinity driven by phosphorus gradients directs Cd/As partitioning in rice - Jibo Long; Qian Zhu; Hongyu Fu; Bingyu Li; Yimin Zhou; Zhuoqing Li; Jiaxiang Wang; Cheng Qiu; Qinghai Liu; Ming Lei (Cereal Research Communications, 2026)

Novel microfluidic gelatin-paper-based chip for sensitive colorimetric detection of urine albumin - Chien-Hsuan Ko; Chin-Chung Tseng; Hsing-Meng Wang; Chia-Chun Lee; Cheng-Xue Yu; Lung-Ming Fu (Analytica Chimica Acta, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Neuromuscular control mechanism during posture-cognition dual task in mild cognitive impairment: a concurrent fNIRS-sEMG-COP study - Ruochen Fu; Jinjin Ma; Yao Zu; Yingying Fang; Yan Li; Arnold Y. L. Wong; Xue Cheng; Yan Leng; Jiajia Yang; Chuhuai Wang; Qiuhua Yu (GeroScience, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

A newly designed retaining wall model apparatus for investigating lateral soil arching effect under controlled wall deformation - Cheng-Shuang Yin; Han-Lin Wang; Xiang-Shen Fu; Yue-Hui Sun; Xiao-Hu Zhang; Marawan Shahien (Transportation Geotechnics, 2026)

Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Achieving reversible dispersion and facile modification of dried cellulose nanocrystals using polyethylene glycol dimethyl ether as a superior capping agent - Yue Niu; Lulu Fu; Kaijie Liu; Huiqing Liu; Dan Zhang; Aoran Wang; Hongxiang Xie; Zhi Fan; Minjie Guo; Bowen Cheng (Food Hydrocolloids, 2026)

High-concentration polyethylene and polystyrene microplastics co-exposure shorten insect lifespan and impose ecological risk: Multi-omics evidence from Drosophila melanogaster - Yingyu Liu; Cheng Wang; Caixia Wang; Longhuan Fu; Yunbo Zhang; Zhuo Gao; Zhugen Yang; Fanyu Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

In situ H2O2 generation-activation via dual active sites in an electro-Fenton system for actual textile dye wastewater treatment - Yaxiong Zeng; Xiaotian Yang; Xueni Huang; Yulin Wang; Fang Cheng; Donggen Chen; Jie Yu; Luchao Wu; Fang Tao; Hailu Fu (Chemical Engineering Journal, 2026)

Photocatalytic hydrogen production: Materials design, system engineering, and data-driven advances - Gengran Zhai; Junchen Liu; Shiyi Lin; Yifan Cheng; Bin Wang; Qingyao Jiang; Hongwei Fu; Hongxin Zhao; Yuan Lu (Chemical Engineering Journal, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

Nitrogen inhibitors enhance ecosystem multifunctionality through microbial networks in alpine grasslands of the Tibetan Plateau - Fang-Kun Yang; Peng-Yang Wang; Ze-Yang Liu; Fu-Ying Niu; Cheng-Yi Xie; Yi-Ming Gao; Yan-Mei Ma; Yu-Xing Wang; Jia-Cheng Guo; Wen-Ying Wang (Applied Soil Ecology, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Understanding roles of different radicals (·OH, SO4·- and ClO·) in the thiacloprid degradation - Guochun Lv; Yunxi Fu; Guiyin Wang; Zhang Cheng; Zhanbiao Yang; Changlian Xu; Xin Qi; Junzhuo Cai; Xiaoxun Xu (Journal of Environmental Management, 2026)

Multifunctional gradient SEI design via LUMO-guided assembly toward wide-temperature zinc-ion batteries - Mengyao Shi; Zhengtai Zha; Fu Li; Yuzhu Wang; Jianfei Su; Min Cheng; Tianjiang Sun; Zhanliang Tao (Chemical Engineering Journal, 2026)

Oriented hetero-phase engineering modulates spontaneous polarization and band alignment - Yumin Wang; Zhenfei Fu; Zewei Zheng; Cheng Gao; Suiting Ning; Yun Tang; Wei Zeng; Pengfei Fang; Yi Xiong (Chemical Engineering Journal, 2026)

Mn-O bond regulated Fe spin state in FePc/MnO2 heterojunction for efficient oxygen reduction reaction - Min Jiang; Yibo Wang; Yilin Han; Xichen Shao; Ruiqi Cheng; Jiao Zhang; Chaopeng Fu (Chemical Engineering Journal, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Molecular characterization of SnRK2 gene family in Capsicum chinense and functional validation of CcSnRK2.5 under drought stress - Huangying Shu; Yu Zhang; Jiancheng Liu; Liping Zhang; Xu Lu; Zhoubin Liu; Shanhan Cheng; Huizhen Fu; Zhiwei Wang (Plant Cell Reports, 2026)

Quercetin inhibits glycolysis and tumor progression in a cell line-dependent manner, involving PI3K/AKT signaling predominantly in HOS cells - Yang Zhou; Liquan Wang; Kang Cheng; Jingwen Chen; Jiale Lv; Chao Song; Zhijiang Fu; Zongchao Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Study on uniaxial compression characteristics and constitutive model of carbonaceous mudstone soil-rock mixture with rock block proportion and dry-wet cycle - Hong-yuan Fu; Hai-tao Yang; Ling Zeng; Jing-cheng Chen; Yan Wang; Hong-ri Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Improved estimation of evapotranspiration and gross primary productivity by incorporating soil moisture feedbacks into a coupled ecosystem model - Shuai Wang; Yingping Wang; Lu Zhang; Lei Cheng; Xuxin Lei; Chenhao Fu; Yao Lai; Shujing Qin; Pan Liu (Agricultural and Forest Meteorology, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

Overexpression of As3mt Attenuates Sodium Arsenite Induced Ferritinophagy and Hepatic Lipid Accumulation in Mice - Jia-cheng Bao; Yuan Yang; Yi Wang; Fu-sheng Xie (Biological Trace Element Research, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Oceanic deoxygenation linked to enhanced water column stratification in the eastern Tethys during Cretaceous Oceanic Anoxic Event 2 - Yu Liang; Yong-Xiang Li; Hongxuan Lu; Huanye Wang; Cece Wang; Cheng Quan; Weiguo Liu; Mei-Fu Zhou; Zhonghui Liu (Global and Planetary Change, 2026)

Proanthocyanidins in food and health: structure–activity relationships, application challenges, and emerging strategies - Ziyu Li; Wenjun Wang; Ping Cheng; Qirong Dong; Haiqi Chen; Kai Fu; Chao Fu; Yunfeng Pu; Donghong Liu (Food Chemistry, 2026)

Pre-acidification modulates stretchability of casein gels via multi-scale structural remodeling mechanisms of hydrogen bonding-calcium phosphate network coupling - Zhaorui Li; Yixiao Wang; Baifeng Fu; Jinxiu Xu; Shuzhen Cheng; Ming Du (Food Hydrocolloids, 2026)

Optimizing the yield-quality balance in wheat by enhancing N uptake and allocation through split N application at the booting stage - Wei Wu; Yang Wang; Huasen Xu; Boyang Fu; Zhengping Peng; Christoph-Martin Geilfus; Cheng Xue (Field Crops Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Green upcycling of tigogenin from sisal waste: Chemoenzymatic cascade synthesis of progesterone derivatives as an alternative to traditional steroid production processes - Lu Song; Zhi-Kun Luo; Fu-Cheng He; Lan-Ya Huang; Liang-Bin Xiong; Yong-Jun Liu; Dong-Zhi Wei; Feng-Qing Wang (Chemical Engineering Journal, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Cellulose helical foam with multi-strategy optical metasurface via synergistic light trapping for superior interfacial solar energy generation - GuanZheng Wu; Wanquan Cai; Zechang Wei; Yibo Wang; Jiawen Ji; Jing Liu; Fulin Cheng; Chenyang Cai; Yu Fu (Carbohydrate Polymers, 2026)

Characteristics and expression of the BES1 transcription factors family in foxtail millet (Setaria italica) reveal its potential roles in drought stress responses - Xueyan Xia; Xiaohong Fu; Yu Zhao; Jihan Cui; Nuoya Xiao; Meihong Huang; Yiwei Lu; Jingxin Wang; Cheng Chu; Shunguo Li; Mingwei Ding (Cereal Research Communications, 2026)

Stable network complexity between bacterial community and dissolved organic matter remains under three-year consecutive nitrogen addition - Xiaochun Yuan; Quanxin Zeng; Qiufang Zhang; Cheng-Chung Liu; Junjian Wang; Liang Zeng; Kaimiao Lin; Chaoliang Chen; Weifeng Guo; Jiacong Zhou; Juyan Cui; Xiaoli Gao; et al. (Applied Soil Ecology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

An enhanced cow-teat-detection model for automatic teat-cup-attachment devices - Mengjie Li; Juan Wang; Na Li; Yaju Liu; Xue Cheng; Xinpei Fu; Sirui Li (Biosystems Engineering, 2026)

Two unprecedented 2-(2-phenylethyl)chromone dimers from the Cambodian agarwood of Aquilaria crassna - Yan Huang; Hao Wang; Wen-Li Mei; Hui-Qin Chen; Fei Wu; Yan-Mei Wei; Wen-Ming Cheng; Hao-Fu Dai (Phytochemistry Letters, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

Carbonate rock dissolution regulates soil microbial iron and nitrogen cycle to reduce cadmium accumulation in rice - Fengling Liu; Hu Wang; Xu Mao; Jianbo Cheng; Bing Wang; Chengwu Fan; Tengbing He; Tianling Fu (Applied Soil Ecology, 2026)

Insights into land deformation processes in the Yellow River Delta (China) from synthetic aperture radar interferometry time series and machine learning - Pengfei Ge; Mi Chen; Roberto Tomás; Hui Liu; Kailun Fan; Xi Cheng; Xingyuan Fu; Shuang Wang (Advances in Space Research, 2026)

Spatiotemporal modeling of oxygen transport and layered regulation in tidal flow constructed wetlands - Rui Ma; Lanlan Fu; Jiangsen Ma; Lei Jiang; Yiyuan Zhuo; Linsong Cheng; Fangying Ji; Xiaoming Wang (Water Research, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Experimental study on monitoring model of bearing capacity characteristics of uplift piles based on flexible piezoelectric sensing - Jun Wang; Xinzhe Tang; Zhiming Liu; Cheng Zhang; Junfeng Ni; Ziyang Gao; Hongtao Fu; Xueyu Geng; Chaoyue Wu (Transportation Geotechnics, 2026)

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

On-demand thermal regulation and water harvesting via liquid metal-infused bio-inspired microchannel architectures - Chenfei Zhou; Yuanbo Sun; Yu Cheng; Chenyang Cai; Meng Zhang; Wang Zhang; Yu Fu (Journal of Cleaner Production, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

A synergistic catalyst of Fe/ZSM-5 for robust aromatics production via methane dehydroaromatization - Xiaohui Wang; Zhilong Cheng; Bingrong Liu; Huiyi Liu; Xin Fang; Ruiqi Chai; Lishuang Ma; Yuchao Lyu; Jianye Fu; Xinmei Liu (Fuel, 2026)

Effects of galactomannan on the quality and component structure of hot-dry noodles during freeze-thaw cycles - Liuyu Wan; Yang Fu; Zhonghua Yuan; Peili Lin; Nian Cheng; Shensheng Xiao; Wenping Ding; Xuedong Wang (Food Chemistry, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Microdroplet air-water interfaces as nanoreactors: Reshaping the atmospheric fate and multiphase risks of phthalates via NO3-initiated interfacial oxidation - Pengcheng Zou; Xueyu Wang; Sisi Cheng; Xusheng Chen; Yuezu Fu; Haiying Yu (Environmental Pollution, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Mechanical interlocking enhanced hybrid electrode for long-term epidermal biopotential monitoring in clinical applications - Xiaoqian Dong; Fu Fan; Lei Chen; Yu Zhou; Fangqun Cheng; Yinglong Duan; Ning Qin; Huan Cao; Xingxing Wang; Bo Feng; Jianfei Xie; Jian Zhou; et al. (Chemical Engineering Journal, 2026)

Insights into the enhanced flux and robust desalination of hydrogel composite Janus membrane in membrane distillation: overlooked interfacial compatibility - Shu Jiang; Anqi Luo; Shilei Fu; Yanrui Wang; Kexin Hou; Jun Ma; Longfeng Hu; Nuo Cheng; Xiaobin Tang; Heng Liang (Chemical Engineering Journal, 2026)

An integrated microfluidic system equipped with a shear force control device for optimized selection of high-affinity, high-specificity aptamers targeting folate receptor alpha - Yang-Sheng Shao; Yi-Cheng Tsai; Chih-Hung Wang; To-Wen Chen; Keng-Fu Hsu; Gwo-Bin Lee (Analytica Chimica Acta, 2026)

Investigation of Pullout Capacity Characteristics of Suction Anchors Under Inclined Loads in Layered Soil - Cheng-Liang Ji; Xia-Tao Zhang; Hao-Yu Wang; Le-Le Liu; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Suction anchors are widely used in marine engineering because of their easy installation, cost-effectiveness, and excellent load-bearing capacity. However, existing research on their bearing capacity has primarily focused on homogeneous soils, which fails to adequately reflect the actual bearing capacity of layered seabed soils. Therefore, this study conducted a series of numerical simulations to investigate the pullout bearing capacity of suction anchors subjected to inclined loads in upper-stiff–lower-soft layered clay. By considering the clay strength (Sum/kD) and soil layer thickness ratio (Th/L, Tc/L), this study systematically explores the influence of the optimal centerline loading depth (Zcl,opt), uniaxial ultimate bearing capacity (Hult and Vult), and the VH failure envelope of suction anchors. The results indicate that the layer thickness ratio Th/L of lightly overconsolidated clay (LOC) is the key factor influencing the Zcl,opt and ultimate bearing capacity Hult and Vult. An increase in Th/L significantly enhances the pullout resistance of suction anchors, which primarily results from the combined enhancement effect of lateral friction resistance and end resistance at the anchor–soil interface. The layered clay has a distinct influence on the horizontal and vertical bearing capacities of suction anchors. Based on the results of parameter analysis, a conservative analytical expression for the lower bound of the VH failure envelope curve is further proposed. The research conclusions provide a theoretical basis and engineering practice guidance for the optimized design and safety assessment of suction anchors in layered soil.

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Machine learning-based prediction of PAHs thermal desorption efficiency: Model optimization, boundary correction, and mechanistic insights - Pengcheng Fu; Meng Qi; Chunshuang Liu; Cheng Zhang; Yuhao Zhao; Zhibao Liu; Hao Wang; Dongfeng Zhao (Journal of Environmental Management, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Neurophysiological and multimodal sensory evaluation of baijiu and food pairing liking - Yu Fu; Cheng Wang; Guoliang He; Shaohui Fan; Deliang Wang; Gaochong Lv; Lucas P.J.J. Noldus; Ting Jiang; Jie Huangfu (Food Research International, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Performance and mechanism of a bimetallic MIL-53(Fe/Co)/MoS₂ heterojunction catalyst for visible-light-driven peroxymonosulfate activation in tetracycline degradation - Weihan Chen; Zhan Wang; Xingping Fu; Miaomiao Wang; Qi Huang; Qianqian Chen; Zhiqiang Wang; Xiaobing Yang; Gao Xiao; Kejun Cheng (Chemical Engineering Journal, 2025)

Ultrafast 1O2 production fulfilled by establishment of interlayer-electron-rich B N3 sites under visible light - Wendi Xu; Yan Wang; Huifeng Fu; Xun Zhou; Meirong Zhou; Jueliang Lu; Cheng Yan; Lihui Zhu; Zhao Hu; Ziru Liu (Chemical Engineering Journal, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Tandem kinase-NLR pairs grant wheat resistance to fungal diseases - Manman Zhang; Cheng Li; Daowen Wang; Fengquan Liu; Zheng Qing Fu (Science China Life Sciences, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

DDX1 facilitates lenvatinib resistance in hepatocellular carcinoma through regulating ephrin-A3 and activating the Wnt/β-catenin signaling pathway - Shenglan Huang; Hua Wang; Shumin Fu; Fei Cheng; Kan Liu; Jianbing Wu (Functional & Integrative Genomics, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Ultrasonic high efficiency preparation of arctigenin from the fruits of Arctium lappa L using Aspergillus niger with deep eutectic solvent assisted - Yubin Ren; Shuang Jin; Weili Liu; Cailiang Peng; Hongyao Cai; Huayong Zhao; Yupeng Cheng; Yujie Fu; Na Zhang; Siyuan Wang; Chen Lv (Biotechnology Letters, 2025)

Amino acid substitutions associated with adaptation of novel H10N3 and H10N5 avian influenza viruses to mice - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

Optimizing rotation lengths of major plantation species for improved wood production in southern China - Minyu Dou; Zhen Wang; Tingshuo Zhang; Zhixin Cheng; Jun Zhang; Wenzheng Fu; Markku Larjavaara; Wennong Kuang; Demeng Jiang; Fangyuan Hua (Forest Ecology and Management, 2025)

How does thinning affect the photosynthetic parameters and their responses to environmental factors in a subtropical plantation? - Mingjie Xu; Shengtong Li; Fengting Yang; Tao Zhang; Qingkang Li; Zeqing Ma; Xianjin Zhu; Xiaoli Fu; Xiaoqin Dai; Jiaxin Song; Ning Chen; Jiaxing Zu; et al. (Forest Ecology and Management, 2025)

Preparation of stir bars coated with N-modified COFs and application to estrogen detection in dairy products - Xixi Lian; Lianzhi Wang; Jianing Sun; Yingying Fu; Zhengchao Duan; Yazhuo Wang; Che Zhao; Gangqi Cheng; Rui Shan (Food Chemistry, 2025)

Development of iterative genome-editing method based on a Rock-Paper-Scissors strategy in Clostridium tyrobutyricum for butyl butyrate from lignocellulosic biomass hydrolysate - Fating Ye; Jun Feng; Xiaolong Guo; Jiale Cheng; Hongxin Fu; Jufang Wang (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Establishment of pollen tube-mediated genetic transformation technique of Primula forbesii - Sitong Fu; Weijia Si; Ying Liu; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Ferrate meets carbon nanotubes: Unraveling the catalytic pathways for enhanced oxidation efficiency of polycyclic aromatic hydrocarbons - Zhiliang Zhao; Leilei Xiang; Yu Liu; Jichan Qian; Yuhao Fu; Jean Damascene Harindintwali; Yongrong Bian; Cheng Fang; Xin Jiang; Fang Wang; Ravi Naidu (Journal of Hazardous Materials, 2025)

Nondestructive classification of internal defects in camellia seeds and chestnuts using X-ray imaging: optimization and comparison of deep learning classifiers - Menglong Ma; Haitao Fu; Yixiao Wang; Zelin Lu; Ziwei Wang; Jingjing Cheng; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Control, 2025)

RBCK1 enhances antiviral response through promoting K63-linked polyubiquitination of IRF7 in Carassius auratus var. Pengze - Quanling Zhang; Tingting Yu; Zhongwei Wang; Miaomiao Li; Jingen Xu; Xuefeng Liu; Cheng Qian; Zijia Yin; Gang He; Menglei Hu; Binchao Zhang; Jiwei Liu; et al. (Fish & Shellfish Immunology, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Inserting sodium lignosulfonate into multilayer graphene in boosting the interfacial polarization of triboelectric nanogenerators for monitoring the impact state of fruits - Meiyi Chen; Xin Li; Tianshuang Bao; Cheng Cai; Yehan Tao; Jie Lu; Chenglong Fu; Jinwen Hu; Jun Xie; Xiaodong Xia; Xuejiao Wang; Jian Du; et al. (Chemical Engineering Journal, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

Biphasic continuously composite electrolyte design for high-performance solid-state Li–CO2 batteries - Qian-Cheng Zhu; Shu-Jian Li; Zi-Yuan Wang; Fu-Li Zhang; Jin-Hao Xie; De-Yu Mao (Chemical Engineering Journal, 2025)

van der Waals heterojunction-based NO2 chemosensor via a synergistic halogen bond site - Wen Luo; Huan Liu; Zhen Zhu; Bo Wang; Wenxing Xu; Ximeng Luo; Chunhui Li; Yanyan Fu; Huizi Li; Huimin Cao; Wei Xu; Qingguo He; et al. (Chemical Engineering Journal, 2025)

Highly sensitive, room-temperature hydrogen sulfide gas sensor based on tungsten trioxide/laser-induced graphene - Li Yang; Longbiao Mao; Zihan Wang; Wenyuan Fu; Luxiang Xu; Chengpeng Yao; Hui Zhang; Huanyu Cheng (Chemical Engineering Journal, 2025)

The critical role of OsYTH10 in promoting early flowering of rice under long sunlight - Jun Yang; Zhihao Chen; Peng Wang; Mvuyeni Nyasulu; Qin Cheng; Xiaopeng He; Jie Xu; Junru Fu; Dahu Zhou; Linjuan Ouyang; Haohua He; Jianmin Bian (Theoretical and Applied Genetics, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Downregulation of Tra2α and Tra2β suppresses lipopolysaccharide-induced inflammation in macrophages by regulating MyD88 mRNA alternative splicing - Yu Fu; Luyao Zhang; Yanjing Wang; Bo Cheng; Weiye Shi; Peiyuan Chen; Jinyu Liu; Xiaolei Zhou; Yingze Wang (Molecular and Cellular Biochemistry, 2025)

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

All-screen-printed tactile sensor for robotic arm via polymeric thermal foaming - Xun Fu; Yugang Chen; Shuting Xie; Mengyu Cao; Qiang Zhao; Yixiao Liu; Yang Li; Shasha Wang; Xiaogang Cheng; Linghai Xie (Chemical Engineering Journal, 2025)

Enhancing Mnammox-driven nutrient removal in manganese ore-based constructed wetlands: The electron-shuttling role of straw-released humus - Rui Ma; Yiyuan Zhuo; Jintao Lei; Lanlan Fu; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2025)

Lanthanum-based hydrogels for simultaneous removal of trace phosphorus and algae - Yan Zhang; Qian Xie; Cheng Fu; Zhen Qiu; Zechao Zhuang; Ting Wang; Yunying Fang; Yongfu Li; Yanjiang Cai; Huajun Feng; Bing Yu (Chemical Engineering Journal, 2025)

ZnO/LIG nanocomposites to detect acetone gas at room temperature with high sensitivity and low detection limit - Li Yang; Wenyuan Fu; Ya Wang; Zhida Wang; Longbiao Mao; Luxiang Xu; Chengpeng Yao; Hongyu Zhang; Sisi Chen; Hui Zhang; Huanyu Cheng (Chemical Engineering Journal, 2025)

Structural and photosynthetic improvement of Myriophyllum aquaticum plant traits through artificial adjustments - Daomin Cheng; Peili Fu; Qingqing Wang; Wei Li; Longyi Yuan; Yang Liu; Yu Cao (Aquatic Botany, 2025)

Coupling effect of phytic acid and chlorite on uranium removal by Shewanella putrefaciens under simulated natural environment - Qingrong Li; Yang-Yang Zhang; Guo-Hao Zhang; Yilin Qin; Wencai Cheng; Xinyu Wang; Liuyuan Fu; Nan Wang; Xiaoan Li; Faqin Dong; Jun Li; Xiaoqin Nie (Water Research, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Research on improving injection and production gas capacity based on integrated reservoir-well coupling model for gas storage - Yu Fu; Ganlin Yuan; Yong Xia; Mingwei Wang; Yunjun Zhang; Xufeng Yang; Zibo Wang; Yuxin Cheng (Fuel, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

Extremely positive δ13C and subsurface CO2 phase separation isotope fractionation - Cheng Wang; Wenxuan Hu; Xun Kang; Xiaolin Wang; Bin Fu; Suping Yao (Chemical Geology, 2025)

Characterization and Risk Assessment of Heavy Metals in Topsoil of Agricultural Land from an Agate Dyeing Village - Haodong Wang; Ye Li; Jia Fu; Shanshan Feng; Quanguo Cheng; Jianbing Wei (Water, Air, & Soil Pollution, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Study on the influence mechanism of raw potato flour on the stability of ketchup - Boqing Fu; Jiahui Fang; Zhengbiao Gu; Yan Hong; Li Cheng; Xu Wang (Food Chemistry, 2025)

Double-layer nanopesticide for duckweed management: Employing natural α-Terthienyl to disrupt the leaf epidermal to enhance the efficacy of prometryn - Ruiquan Hou; Guofu Fu; Shuyi Ma; Shiqi Tang; Feng Guo; Yongqing Wang; Suqing Huang; Dongmei Cheng; Zhixiang Zhang; Chen Zhao (Chemical Engineering Journal, 2025)

Nano-sized coordination polymer particles (CPPs) for synergetic application in antibacterial and anticancer therapeutics - Wang Ding; Tikai Zhang; Ruiying Fu; Chengtao Yu; Cheng Zhang; Kuaibing Wang; Pengfei Zhang (Chemical Engineering Journal, 2025)

Integration of moving bed biofilm reactor and gravity-driven membrane bioreactor for decentralized domestic wastewater treatment: Efficiency and mechanistic insights - Zixin Ma; Ziao Zhang; Shilei Fu; Linqiao Jiang; Yitong Sun; Yichun Zhu; Yanrui Wang; Wenjun Cheng; Xiaobin Ma; Heng Liang; Xiaobin Tang (Bioresource Technology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Unsupervised SAR image change detection using multi-level graph attribute matching - Jun Wang; Qiongjun Fu; Jiahui Li; Sanku Niu; Yaohui Zhu; Yuechao Zhang; Pengle Cheng (International Journal of Remote Sensing, 2025)

Adaptation and synthetic biology of the model cyanobacterium Synechococcus elongatus for sustainable development: a review - Weizhao Meng; Mengsheng Xia; Jingyan Hu; Chao Wang; Cheng Qian; Mingmin Zhang; Weiqi Fu (Frontiers in Marine Science, 2025)
Synechococcus elongatus is a model cyanobacterium with remarkable adaptability to diverse environmental stresses, making it a promising candidate for the photoautotrophic conversion of carbon dioxide into valuable chemicals. This review explores the adaptive mechanisms that allow S. elongatus to survive under various abiotic stresses, such as changes in CO 2 levels, heavy metals, and light conditions. We also highlight recent advancements in synthetic biology that have enabled the engineering of S. elongatus to produce biofuels and other value-added compounds, including fatty acids, alcohols, and carotenoids. Additionally, we discuss the applications of modern omics techniques to elucidate the genetic basis of stress tolerance and metabolic regulation. Despite the promising potential of S. elongatus for industrial applications, challenges remain in scaling up production, enhancing genetic stability, and optimizing bioreactor systems. Finally, we provide insights into future directions, including the integration of genome engineering, system-level modeling, and co-culture strategies, to improve the efficiency of cyanobacterial cell factories for sustainable biotechnology applications.

Chinese cities show disparity trends in carbon efficiency: A hybrid approach combining explainable machine learning and econometrics - Le Ma; Tong Cheng; Longgang Xiang; Chao Wang; Liyuan Wei; Jianing Wang; Chaoya Dang; Wenjie Fu; Huayi Wu (Sustainable Cities and Society, 2025)

Antibiotic resistance gene transfer characteristic and risk evaluation: The entire process from swine manure to biogas slurry and then to soil - Pengcheng Liang; Hu Wang; Quanxu Chen; Qu Luo; Jianbo Cheng; Guangliang Tian; Tengbing He; Wenhai Zhu; Tianling Fu (Journal of Environmental Chemical Engineering, 2025)

Exogenous cysteine-induced unfolding of soy protein enhances the solubility and stability of astaxanthin - Guangbin Zhang; Shuzhen Cheng; Bowen Zou; Baifeng Fu; Yixiao Wang; Zhenyu Wang; Ming Du (Food Bioscience, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

New Colorimetric Chemosensor for Rapid Naked-Eye Detection of Cu2+ and Its Application in Gas-Generating Agents - Xiaohong Cheng; Jun You; Shaoyong Meng; Wenjie Shen; Tao Du; Wenbin Fu; Yunqiang Luo; Song Wang (Journal of Fluorescence, 2025)

Microbial metabolism in wormcast affected the perturbation on soil organic matter by microplastics under decabromodiphenyl ethane stress - Yanna Han; Mengru Fu; Yuhe Yang; Zhiyin Zhang; Tianzi Liu; Shanqi Zhou; Zhihua Qiao; Gehui Wang; Cheng Peng; Wei Zhang (Journal of Hazardous Materials, 2025)

Morphologically regulated nanocellulose from soybean residues for stabilizing Pickering emulsions via interfacial interaction - Yanyi Xue; Wenliang Wang; Xinyi Zheng; Xiufeng Duan; Xiaoxiao Ren; Yishuai Fu; Jinbao Cheng; Chengyuan Liang (Food Hydrocolloids, 2025)

Mechanistic insights into the preparation and electrodeposition characteristics of Cu–Fe powder employing magnetic field fluidized bed electrode - Hongtao Li; Haitao Yang; Jiaxin Cheng; Xin Wang; Guohui Fu; Liansheng Xu; Qingping Chai (Chemical Engineering Journal, 2025)

3D printing of synthetic microbial consortium for boosting bioelectricity generation from starch - Xiao-Jing Wang; Jie Wang; Zhizhi Yang; Ye Zhang; Kai Cheng; Jun-Ying Han; Fu-Xiang Chang; Yang-Chun Yong (Chemical Engineering Journal, 2025)

Novel polymersomes based on Poly(2-methyl-2-oxazoline) polymers with excellent pharmacokinetic behavior and antitumor effect by modulating dynamic protein corona - Zimin Cai; Fangqin Fu; Sifeng Zhu; Jibin Wu; Xu Han; Shuai Jiang; Zhiyong Qian; Cheng Wang (Chemical Engineering Journal, 2025)

Composite of mixed-cation perovskite MA1-FA PbI3 with MoSe2 for enhanced photocatalytic H2 evolution - Hui Fu; Qianqian Zhang; Yaqiang Wu; Zeyan Wang; Yuanyuan Liu; Zhaoke Zheng; Hefeng Cheng; Baibiao Huang; Peng Wang (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Five-year-old children with autism spectrum disorders struggle with disengaging attention - Wei Wang; Chun Cheng; Zhiyu Xu; Licheng Xue; Wanlu Fu; Jing Zhao (Cognitive Processing, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Genome skimming for improved phylogenetics of Taiwanese phasmids (Insecta: Phasmatodea) - Bo-Cheng Wang; Ming-Luen Jeng; Jing-Fu Tsai; Li-Wei Wu (Molecular Phylogenetics and Evolution, 2025)

Fucoxanthin promotes the conversion efficiency of alpha-linolenic acid in feeding to docosahexaenoic acid in quail egg yolk - Wen-Lei Guo; Shuai-Shuai Fu; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Yu-Ming Wang; Tian-Tian Zhang (Food Chemistry, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

Dry season residual straw reduces nitrous oxide emissions during rice season in upland-paddy rotation systems by inhibiting soil denitrification - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Zhiping Yang; Yong Fu; Xueping Yue; Fei Deng; Xiaolong Lei; et al. (Biology and Fertility of Soils, 2025)

Cold stress changes the intestinal oxidative stress-mediated MAPK pathways and lipid metabolism in Takifugu fasciatus - Yuxi Liu; Xuechun Zang; Cheng Zhao; Peng Chu; Heyu Chen; Dongyong Fu; Sijin Wang; Kai Zhang; Tao Wang; Shaowu Yin (Aquaculture, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Photocatalytic degradation of xanthate by S–scheme CeO2/g–C3N4 heterojunction and its DFT calculation - Deqin Meng; Li Wang; Cheng Zhong; Jiani Fu; Xiaolong Hu; Dengzheng Gao; Qingbin Guo; Jinbo Hou; Hang Zhao (Journal of Water Process Engineering, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Enhanced heat retention and energy efficiency in photothermal membranes via sealed light-absorbing cavity engineering - Yibo Wang; Yuanbo Sun; Fulin Cheng; Zechang Wei; Chenyang Cai; Yu Fu (Chemical Engineering Journal, 2025)

Ammonia inhibition in anaerobic digestion of organic waste: a review - J. Yang; J. Zhang; X. Du; T. Gao; Z. Cheng; W. Fu; S. Wang (International Journal of Environmental Science and Technology, 2025)
Anaerobic digestion (AD) has become the technology of choice for organic waste treatment as an environmentally beneficial and sustainable waste treatment technology. However, the nitrogen content of these organic waste streams is generally high. Ammonia is produced in the biodegradation of nitrogenous organic matter. Low concentrations of ammonia favour AD, but high concentrations can lead to digestive system failure. To address the issue of ammonia inhibition and ensure the stability of the digestive system, numerous physical, chemical, and biologicalmethods aimed at controlling ammonia levels and/or strengthening the biological processes have been proposedand developed. Literature evidence suggests that differences in AD reaction conditions and microbial sources result in different tolerances of the digestive system to ammonia and nitrogen. This paper summarises and compares the inhibitory effects of ammonia nitrogen under different conditions and the existing regulatory measures to alleviate ammonia nitrogen inhibition. In addition, since the core of the digestive system is microorganisms, this paper explains the mechanism of ammonia stress especially at the microbial level, and in this way, it explores the future direction of research using biofortification. This review provides a theoretical reference for solving the problem of ammonia nitrogen inhibition.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The induction of polyamines metabolism pathway and membrane stability with silicon alleviate the vanadium toxicity in pepper plants - Naveed Mushtaq; Muhammad Ahsan Altaf; Huangying Shu; Xu Lu; Shanhan Cheng; Mohamed A. El-Sheikh; Parvaiz Ahmad; Huizhen Fu; Zhiwei Wang (Journal of Hazardous Materials, 2025)

Directional anchoring of polymer-lysozyme nanohybrids for adhesive capture and enhanced removal of Alicyclobacillus acidoterrestris in fruit juices - Bingzhi Li; Kun Cheng; Lunjie Huang; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Bangfeng Fu; Maojun Jin; et al. (Food Chemistry, 2025)

Integrated network pharmacology, bioinformatics, and experiment analysis to decipher the molecular mechanism of Salidroside on Gastric cancer via targeting NCOA4-mediated ferritinophagy - Yu Fu; Guiqin Huang; Yawen Cai; Menghui Ren; Run Cheng; Yuhui Chai; Yingdi Wang; Yunqi An; Tianhua Yan; Lingpeng Zhu; Xinxin Liu (Chemico-Biological Interactions, 2025)

Hot syngas cleanup for pilot two-stage fluidized bed steam-oxygen biomass gasification plant - Zhijie Fu; Nazanin Charchi Aghdam; Sahand Nekoeian; Jing He; Long Cheng; Shida Liu; Lei Zhang; Junnan Chao; Xiaoyang Wei; Ruixu Wang; Bhavya Nagda; Yumeng Zhang; et al. (Bioresource Technology, 2025)

Consolidated bioprocessing of cassava starch into butyric acid and butanol by engineered Clostridium butyricum SCUT 620 - Hongxin Fu; Xin Li; Xiaolong Guo; Die Yang; Chenchen Nan; Jiale Cheng; Haoming Du; Mengju Shen; Jufang Wang (Bioresource Technology, 2025)

The Role of the Dysregulation of circRNAs Expression in Glioblastoma Multiforme - Yafei Wang; Ying Yu; Jiahua Yu; Cheng Wang; Yunkun Wang; Runxi Fu; Chenran Zhang (Journal of Molecular Neuroscience, 2025)

A Novel Coumarin Based Fluorescent Probe for Cu²⁺ Detection as well as Applications - Yunke Gao; Linlong Deng; Lei Xue; Yihan Cheng; Shuai Fu; Haibin Wang (Journal of Fluorescence, 2025)

Mechanism of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid toxicity in Carassius auratus through the microbiota–gut–brain axis - Xue Jiao; Faye Zhang; Lei Guo; Zheng-Yao Guo; Qiu-Shuang Fu; Cheng-Cheng Bi; Xian-Wei Hou; Ning Wang; Jing-Xiang Zhou; Yue-Hong Li (Aquaculture, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Electrochemical upcycling strategy for polyethylene terephthalate plastic coupled with efficient hydrogen production - Xingye Lu; Yuhao Guo; Hui Fu; Jia Song; Congcong Liang; Hechun Jiang; Zeyan Wang; Yuanyuan Liu; Hefeng Cheng; Zhaoke Zheng; Yaqiang Wu; Peng Wang; et al. (Chemical Engineering Journal, 2025)

In-situ packing self-intumescent aerogel particles in rigid polyurethane foam towards thermal insulation, flame retardance and smoke suppression - Ning Yu; Ting Wang; Cheng-Xu Xu; Xue Gou; Ying-Jiao Zhan; Wenli An; Zhi-Cheng Fu; Jinni Deng; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Construction of a physical map for Aegilops geniculata chromosome 7Mg and localization of its novel purple coleoptile gene - Huanhuan Li; Fu Guo; Yanlong Zhao; Chaoli Wang; Ziwei Fan; Yajun Feng; Xiang Ji; Luna Tao; Chao Ma; Jiajun Qian; Yue Zhao; Qianwen Liu; et al. (Theoretical and Applied Genetics, 2025)

Manganese(III) dominants the mobilization of phosphorus in reducing sediments: Evidence from Aha reservoir, Southwest China - Quan Chen; Jing-fu Wang; Meng-qiang Zhu; Hai-bo Qin; Peng Liao; Zhi-tong Lu; Peng-cheng Ju; Jing-an Chen (Science of The Total Environment, 2024)

Mapping urban construction sites in China through geospatial data fusion: Methods and applications - Chaoqun Zhang; Ziyue Chen; Lei Luo; Qiqi Zhu; Yuheng Fu; Bingbo Gao; Jianqiang Hu; Liurun Cheng; Qiancheng Lv; Jing Yang; Manchun Li; Lei Zhou; et al. (Remote Sensing of Environment, 2024)

H2O2 sulfenylates CHE to activate systemic salicylic acid synthesis and ignite systemic acquired resistance - Kaihuai Li; Cheng Li; Daowen Wang; Fengquan Liu; Zheng Qing Fu (Molecular Plant, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Facet-induced fractionation of humic acid by hematite and the promoted-photodegradation of 17β-estradiol catalyzed by hematite-humic complex - Ziyan Zhou; Hao Wu; Boming Fu; Dingding Wu; Xinhao Wang; Davide. Vione; Xin Jin; Yanfen Fang; Cheng Gu (Journal of Hazardous Materials, 2024)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

N6-methyladenosine demethylase FTO regulates neuronal oxidative stress via YTHDC1-ATF3 axis in arsenic-induced cognitive dysfunction - Lixiao Zhou; Renjie Li; Fu Wang; Ruiqi Zhou; Yinyin Xia; Xuejun Jiang; Shuqun Cheng; Fanghong Wang; Danyang Li; Jun Zhang; Lejiao Mao; Xuemei Cai; et al. (Journal of Hazardous Materials, 2024)

Delving into textile fast pyrolysis: A holistic study on the effects of feedstock and temperature variability - Yoke Wang Cheng; Jiaqing Huang; Xueying Tang; Wenming Fu; Dequan Xu; Chi-Hwa Wang (Journal of Cleaner Production, 2024)

Variations in volatile components and biological activities of essential oils from Citrus aurantium ‘changshanhuyou’ at different growth and ripening stages - Han Wang; Xinyue Zhou; Yong Deng; Ruyu Zhang; Kai Fu; Jiabao Huang; Qiong Huang; Cheng Zeng; Donghong Liu; Wenjun Wang (Food Research International, 2024)

Sheep skin collagen peptide exerts an anti-fatigue effect by improving energy metabolism via AMPK/PGC-1α axis and reducing oxidative damage via NRF2/HO-1 axis - Xiaoyu Ma; Quanxi Wang; Qi Yang; Ximing Yang; Xinran Liu; Baifeng Fu; Shuzhen Cheng; Ming Du (Food Bioscience, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Active methane release from the early Cambrian seafloor? Clues from Ba isotopes - Meng Cheng (程猛); Wei Wei; Xinyang Chen; Haiyang Wang; Lianjun Feng; Zhenbing She; Yong Fu; Thomas J. Algeo; Fang Huang; Chao Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The effect of structural changes on the activity of peroxidase with different initial state under high-pressure freezing - Zhanhong Liang; Yuanshan Yu; Bo Zou; Manqin Fu; Tenggen Hu; Xiaomeng Yin; Jin Wang; Yujuan Xu; Lina Cheng (Food Chemistry, 2024)

A straightforward strategy to modulate ROS generation of AIE photosensitizers for type-I PDT - Zhencheng Sun; Jiaxin Wang; Minghui Xiao; Kaiyu Wu; Cheng Wang; Hao Fu; Shuyi Lv; Linqi Shi; Chunlei Zhu (Chemical Engineering Journal, 2024)

Interfacial chemical bonds enhanced photocatalytic performance of kaolinite/NiFe layered double oxide heterostructure for photocatalytic activated peroxymonosulfate - Cheng Li; Huihua Jing; Bing Lv; Donghang Zhou; Shuguang Fu; Xiong Tang; Zhengpei Wang; Weiguang Wu; Denghui Jiang (Applied Clay Science, 2024)

Correction to: A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

Hourly effect of atmospheric reactive nitrogen species on the onset of acute ischemic stroke: Insight from the Shanghai Stroke Service System Database - Kun Fang; Lan Hong; Yiran Zhang; Nan Cao; Jialiang Feng; Ming Hu; Qingyan Fu; Yang Zheng; Qundi Yang; Yuzhuo Wang; Jinyitao Wang; Shunyao Wang; et al. (Science of The Total Environment, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Low-grade systemic inflammation links heavy metal exposures to mortality: A multi-metal inflammatory index approach - Yin Wang; Yuyan Wang; Ruizhen Li; Baiwen Ni; Ruixin Chen; Yun Huang; Rongrong Cheng; Pei Li; Han Li; Yang Peng; Xue Chen; Jingyu Wang; et al. (Science of The Total Environment, 2024)

Influences of crop diversification on yield, resource use efficiency, and environmental footprint in farmland landscapes in intensive farming - Xiaohui Wang; Jiali Cheng; Jiaen Zhang; Fu Chen (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Developing a Deep Learning network “MSCP-Net” to generate stalk anatomical traits related with crop lodging and yield in maize - Haiyu Zhou; Xiang Li; Yufeng Jiang; Xiaoying Zhu; Taiming Fu; Mingchong Yang; Weidong Cheng; Xiaodong Xie; Yan Chen; Lingqiang Wang (European Journal of Agronomy, 2024)

PCAF-mediated acetylation of METTL3 impairs mRNA translation efficiency in response to oxidative stress - Cheng Liu; Miao Yu; Mengyuan Wang; Siyuan Yang; Yenan Fu; Lei Zhang; Chaoyang Zhu; Hongquan Zhang (Science China Life Sciences, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

The research and application of technology and core components in commercial refrigeration and freezing Systems：A review - Hailing Fu; Shuo Huang; Yuan Li; Jiasen Cheng; Yang Guo; Kang Wang; Ranran Sun (Journal of Stored Products Research, 2024)

Detoxification and neurotransmitter clearance drive the recovery of Arma chinensis from β-cypermethrin-triggered knockdown - Zhen Wang; Wenjie He; Luyao Fu; Hongmei Cheng; Changjin Lin; Xiaolin Dong; Chenxi Liu (Journal of Hazardous Materials, 2024)

Low-carbon strategy analysis in a construction supply chain considering government subsidies and contract design - Cheng Fu; Wei Yu; Yan Wang; Wenrui Feng; Jianjian Chen (Journal of Cleaner Production, 2024)

3D-printable liquid metal ink for shape-morphing solar evaporator via programmable “freeze-printing” strategy - Wanquan Cai; Zechang Wei; Jiawen Ji; Jing Liu; Yibo Wang; Fulin Cheng; Chenyang Cai; Yu Fu (Desalination, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Fengju Wang; Ruiming Lin; Hongqi Si; Chuanxi Ma; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Counteractive catalytic effects of FeNi- versus Fe- and Ni- in plastic pyrolysis for advanced-quality jet fuel production - Wenming Fu; Yoke Wang Cheng; Yiying Wang; Yaning Zhang; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Converting fruit peels into biodegradable, recyclable and antimicrobial eco-friendly bioplastics for perishable fruit preservation - Shikai Zhang; Xinxin Cheng; Wenjing Yang; Quanbin Fu; Feng Su; Peng Wu; Yijing Li; Fen Wang; Houshen Li; Shiyun Ai (Bioresource Technology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Integrated Bulk and Single-Cell RNA-Sequencing Reveals the Effects of Circadian Rhythm Disruption on the Metabolic Reprogramming of CD4+ T Cells in Alzheimer’s Disease - Weipin Weng; Jianhan Fu; Fan Cheng; Yixuan Wang; Jie Zhang (Molecular Neurobiology, 2024)

A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Tanshinone IIA, originated from Salvia miltiorrhiza, activated EPO/EPOR-JAK2-STAT5 pathway in rat blood deficiency therapy - Miao Wang; Zhihong Deng; Congwei Shi; Kun Cheng; Runxiang Zhai; Xiuxue Li; Xianjun Fu (South African Journal of Botany, 2024)

PagPXYs improve drought tolerance by regulating reactive oxygen species homeostasis in the cambium of Populus alba × P. glandulosa - Cheng Jiang; Jiawei Wang; Xinyue Fu; Chunyan Zhao; Weilin Zhang; Hesheng Gao; Chenhao Zhu; Xueqin Song; Yanqiu Zhao; Yi An; Lichao Huang; Ningning Chen; et al. (Plant Science, 2024)

Bioconversion of soybean meal into gut microbiota-targeting polysaccharides via fermentation by Bacillus subtilis - Cheng Wang; Yu Zhang; Siyu Wei; LeLe Fu; Yizhen Wang; Mingliang Jin (Journal of Cleaner Production, 2024)

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

An efficient photo-Fenton In2O3@FeIn2S4 composite catalyst for tetracycline degradation - Shengyu Jing; Jing Ren; Anhu Wang; Ruolin Cheng; Huagen Liang; Hai Liu; Fu Chen; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Recent advances in preferentially selective Li recovery from spent lithium-ion batteries: A review - Qian Cheng; Ze Wang; Yue Wang; Jun-Tao Li; Haiyan Fu (Journal of Environmental Chemical Engineering, 2024)

Bimetallic iron-copper nanozyme for determination and degradation of norfloxacin in foods - Cong Cheng; Min Han; Gang Xiang; Xiaoying Fu; Xianxing Wang; Changfang Lu (Food Chemistry, 2024)

The potential benefits of Oreochromis mossambicus derived hydrophobic peptides in protecting the skin against UVA-induced damage - Hui Yao; Siyi Wang; Baifeng Fu; Xianbing Xu; Shuzhen Cheng; Ming Du (Food Bioscience, 2024)

Bi, K co-doped graphitic phase carbon nitride for efficient photocatalytic H2O2 production - Huagen Liang; Anhu Wang; Ruolin Cheng; Fu Chen; Palanisamy Kannan; Costas Molochas; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Biosynthetic potential of uncultured anammox community bacteria revealed through multi-omics analysis - Yi-Cheng Wang; Hui-Min Fu; Yu Shen; Jin Wang; Nuo Wang; You-Peng Chen; Peng Yan (Bioresource Technology, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Enhanced home-field advantage in deep soil organic carbon decomposition: Insights from soil transplantation in subtropical forests - Kuan Liang; Yong Lin; Tiantian Zheng; Fangchao Wang; Yuandong Cheng; Shennan Wang; Chao Liang; Fu-Sheng Chen (Science of The Total Environment, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Nano effect fluorescence visual sensor based on Au-AgNCs: A novel strategy to identify the origin and growth year of Lilium bulbs - Siyu Wang; Wanjun Long; Liuna Wei; Wenyu Cheng; Hengye Chen; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

Efficient production of butyl butyrate from mannitol by engineered Clostridium tyrobutyricum - Xiaolong Guo; Fating Ye; Chenchen Nan; Jiale Cheng; Jun Feng; Hongxin Fu; Jufang Wang (Chemical Engineering Journal, 2024)

Characterization of organic vapors by a Vocus proton-transfer-reaction mass spectrometry at a mountain site in southeastern China - Yi Zhang; Weiqi Xu; Wei Zhou; Yan Li; Zijun Zhang; Aodong Du; Hongqin Qiao; Ye Kuang; Lanzhong Liu; Zhiqiang Zhang; Xiao He; Xueling Cheng; et al. (Science of The Total Environment, 2024)

Potential of combined reactor and static composting applications for the removal of heavy metals and antibiotic resistance genes from chicken manure - Qu Luo; Hu Wang; Xiaoqing Lu; Can Wang; Ruiying Chen; Jianbo Cheng; Tengbing He; Tianling Fu (Journal of Environmental Management, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Self-assembled oxygen vacancies modified hierarchical hollow tubular Bi2WO6/In2O3 Z-scheme heterojunction for optimized photocatalytic degradation of norfloxacin - Xin Wang; Chuangyun Guo; Xinru Hu; Yifei Xu; Cheng Zhang; Jiamin Wei; Jushi Weng; Yilan Liu; Lianshe Fu; Qing Wang; Tinghai Yang (Journal of Environmental Chemical Engineering, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Integration of bulk-surface charge polarization and active site manipulation for highly efficient photocatalytic aerobic oxidation of sulfides - Jun Wan; Yang-Ai Ma; Yina Nie; Junhao Cheng; Chengming Wang; Lin Liu; Feng Fu (Chemical Engineering Journal, 2024)

Cationic cellulose nanofibers/chitosan auxiliary-dominated win-win strategy for paper yarn with superior color and physical performances - Xiaohui Guo; Rendang Yang; Yang Wang; Shuzhen Ni; Chen Cheng; Danning Fu; Jie Sheng (Carbohydrate Polymers, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Exogenous strigolactone enhanced the drought tolerance of pepper (Capsicum chinense) by mitigating oxidative damage and altering the antioxidant mechanism - Huangying Shu; Kaijing Xu; Xiangrui Li; Jiancheng Liu; Muhammad Ahsan Altaf; Huizhen Fu; Xu Lu; Shanhan Cheng; Zhiwei Wang (Plant Cell Reports, 2024)

Occupational exposure to silica and risk of gastrointestinal cancers: a systematic review and meta-analysis of cohort studies - Jiyuan Shao; Pengfei Fu; Shengchun Wang; Hong Cheng; Xin Zhang (International Archives of Occupational and Environmental Health, 2024)

Microplastics: A potential proxy for tracing extreme flood events in estuarine environments - Hongyu Chen; Yu Cheng; Ying Wang; Yongcheng Ding; Chenglong Wang; Xuguang Feng; Qinya Fan; Feng Yuan; Guanghe Fu; Bingfei Gao; Kai Liu; Xinqing Zou (Science of The Total Environment, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Source apportionment and predictable driving factors contribute to antibiotics profiles in Changshou Lake of the Three Gorges Reservoir area, China - Yue Mu; Bobin Tang; Xian Cheng; Yuanhang Fu; Weibin Huang; Jing Wang; Dewang Ming; Liangshu Xing; Jinzhong Zhang (Journal of Hazardous Materials, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

A comparative study on the degradation of carbamazepine by UV laser/chlorine and UV laser/PS processes: Performance and mechanisms - Qi Fu; Xing-Xing Wang; Huan He; Tian-Yang Zhang; Jian Lu; Meng-Yuan Xu; Renjie Pan; Tong-Cheng Cao; Mohamed Gamal El-Din; Bin Xu (Chemical Engineering Journal, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Feeding experience on hairy vetch induces a loss of host-specific adaptation to maize and changes in the gut microbiota communities of the fall armyworm - Lin Ma; Dao-Tong Wang; Qi-Lin Ren; Lei Zhang; Yun-Xia Cheng; Xing-Fu Jiang (Journal of Pest Science, 2024)

Interval aerobic/resistance exercise training depresses adrenergic-induced apoptosis of lymphocytes in sedentary males - Yu-Chieh Huang; Chih-Chin Hsu; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2024)

DNA-induced assembly of biocatalytic nanocompartments for sensitive and selective aptasensing of aflatoxin B1 - Xuan Xu; Junfeng Fu; Xiaotong Jiao; Yuqin Wang; Cheng Yao (Analytica Chimica Acta, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Graphitic carbon nitride coupled with molybdenum selenide composite photocatalyst for tetracycline degradation - Huagen Liang; Anhu Wang; Ruolin Cheng; Fu Chen; Shengyu Jing; Angeliki Brouzgou; Panagiotis Tsiakaras (Journal of Environmental Chemical Engineering, 2024)

Plugging effects by GPM based two-phase flow in gas drainage fracture: A simulation study - Jianwei Cheng; Dezhi Ran; Yiwen Ju; Qiang Fu; Wang Luo (International Journal of Rock Mechanics and Mining Sciences, 2024)

Constructing ion “Tongs” and double-network for cellulose-based semi-solid electrolytes towards dendrite-free dual-ion batteries - Jiawen Ji; Fulin Cheng; Wanquan Cai; Yuxin Ji; Jing Liu; Yibo Wang; Chenyang Cai; Yu Fu (Chemical Engineering Journal, 2024)

Phosphorus-containing active esters modified dicyclopentadiene epoxy resins with simultaneously improved flame retardancy, thermal stability, and dielectric properties - Zhenye Fu; Zirui Ma; Jiuhong Liu; Chunhui Li; Chuanmei Liu; Qidong Wang; Liang Song; Qing Yu; Guiqing Cheng; Yuxi Han; Hailong Liu; Zhongwei Wang (Chemical Engineering Journal, 2024)

Harsh environment resistible and recyclable thermoplastic polyurea adhesive based on stable and density hydrogen bonds - Dongqi Wang; Kai Yang; Sisi Cheng; Meishan Fu; Zhihong Wang; Lixia Li; Xin Zhao; Lijing Han; Wenzhi Ren; Fang Yang; Ruoyu Zhang (Chemical Engineering Journal, 2024)

Revolutionizing aqueous Zn-ion batteries: Precision control of H2O activity and Zn deposition through ammonium oxalate additive - Wenhao Ding; Guolang Zhou; Xiangjie Guo; Cheng Liu; Tianshi Wang; Yongsheng Fu; Jingzhou Yin; Lili Zhang; Edison Huixiang Ang (Chemical Engineering Journal, 2024)

Identification of pigeon mitochondrial antiviral signaling protein (MAVS) and its role in antiviral innate immunity - Qi Shao; Yawen Li; Feiyu Fu; Pei Zhu; Hengan Wang; Zhaofei Wang; Jingjiao Ma; Yaxian Yan; Yuqiang Cheng; Jianhe Sun (Archives of Virology, 2024)

Endoplasmic reticulum stress exacerbates microplastics-induced toxicity in animal cells - Zhanhang Wang; Shujuan Liu; Zefang Cheng; Ganggang Xu; Fu Li; Qiqi Bu; Lei Zhang; Yuxuan Song; Xiaopeng An (Food Research International, 2024)

Synergistic mechanism of surface oxygen vacancies and metal sites on Al-substituted NiFe2O4 during peroxymonosulfate activation in the solid-water interface for 2,4-D degradation - Jinxiang Zuo; Donglei Fu; Pengwei Yan; Shuyu Wang; Yabin Li; Linlu Shen; Yizhen Cheng; Jimin Shen; Jing Kang; Zhonglin Chen (Chemical Engineering Journal, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Efficient photocatalytic production of H2O2 and photodegradation of tetracycline by CdS/square tubular g-C3N4 S-scheme heterojunction photocatalyst - Shengyu Jing; Jingbo Zhao; Anhu Wang; Qiushi Ji; Ruolin Cheng; Huagen Liang; Fu Chen; Palanisamy Kannan; Angeliki Brouzgou; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Chronic cold environment regulates rheumatoid arthritis through modulation of gut microbiota-derived bile acids - Juan Liu; Fu Peng; Hao Cheng; Dandan Zhang; Yuxi Zhang; Lixia Wang; Fei Tang; Jing Wang; Yan Wan; Jing Wu; Yinlin Zhou; Wuwen Feng; et al. (Science of The Total Environment, 2023)

Urban overall and visible greenness and diabetes among older adults in China - Kejia Hu; Zuhui Zhang; Yuanyuan Li; Shiyi Wang; Tingting Ye; Jinglu Song; Yunquan Zhang; Jing Wei; Jian Cheng; Yujie Shen; Jiahao Pan; Jingqiao Fu; et al. (Landscape and Urban Planning, 2023)

Phenanthrene release-migration characteristics and potential influencing mechanisms from paddy soil to overlying water under bioturbation in a rice-fish coculture agroecosystem - Nan Sun; Jin Liu; Zi-Jian Wang; Shuang Liu; Hao Cheng Wang; Qiang Fu (Journal of Cleaner Production, 2023)

Effects of frozen storage on the quality characteristics of frozen whole buckwheat extruded noodles - Ruhui Xia; Meixia Fu; Zhenjiong Wang; Weiwei Cheng; Di Wu; Xiaozhi Tang; Peiqiang Yang (Food Chemistry, 2023)

Molten salt-assisted carbonized zeolite imidazolate framework on nickel foam for highly efficient iodide capture in fluoride molten salts - Ming Cheng; Junxia Geng; Yujiao Wang; Qin Lin; Xiaoyu Zhang; Lixin Sun; Qiang Dou; Haiying Fu (Chemical Engineering Journal, 2023)

Effect of common low-molecular-weight organic acid on the photodegradation of sertraline by ferrihydrite - Ziyan Zhou; Dingding Wu; Hao Wu; Boming Fu; Xinhao Wang; Jingyi Ling; Xin Jin; Cheng Gu (Chemosphere, 2023)

Budget of atmospheric nitrous acid (HONO) during the haze and clean periods in Shanghai: Importance of heterogeneous reactions - Jialiang Feng; Ensi Ren; Ming Hu; Qingyan Fu; Yusen Duan; Cheng Huang; Yue Zhao; Shunyao Wang (Science of The Total Environment, 2023)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Volcanosedimentary fill of the early Cretaceous Yingcheng formation and response to the end of continental rifting in the Songliao Basin: Constraints from well SK-2, northern Xujiaweizi fault depression - Ye Wang; Rihui Cheng; Yanjie Shen; Yu Fu; Zhongjie Xu; Youfeng Gao (Marine and Petroleum Geology, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Long-term anthropogenic field management enhanced wheat productivity and resource utilization in the Loess Plateau region of China - Peng Wu; Gang Zhao; Qi Wu; Hua Huang; Peng Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; Shangzhong Li; Lei Wang; Wanli Cheng; Jian Fu; et al. (European Journal of Agronomy, 2023)

Stabilization of capsanthin in physically-connected hydrogels: Rheology property, self-recovering performance and syringe/screw-3D printing - Hongxia Wang; Chaoyang Wu; Juncheng Zhu; Yang Cheng; Yuxin Yang; Shihao Qiao; Bo Jiao; Liang Ma; Yu Fu; Hai Chen; Hongjie Dai; Yuhao Zhang (Carbohydrate Polymers, 2023)

Seasonal differences in continental outflows and marine emissions of organic aerosols in the East China Sea: Insight from the variation of saccharides - Hao Li; Lan Wang; Xiaofei Qin; Guochen Wang; Mengxin Fu; Cheng Chen; Jian Xu; Congrui Deng; Kan Huang (Atmospheric Research, 2023)

Performance analyses of two-phase closed thermosyphons for road embankments in the high-latitude permafrost regions - Guan-fu Wang; Chuang Lin; Long Zhu; De-cheng Feng; Yang-yang Xin; Feng Zhang (Journal of Mountain Science, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Accumulative responses of soft clayey seabed: A case study from the Eastern Coast of China - Cheng Wang; Kang Yao; Wen Liu; Zunan Fu; Yanming Yu; Li Shi (Marine Georesources & Geotechnology, 2023)

Dissolved black carbon incorporating with ferric minerals promoted photo-Fenton-like degradation of triclosan in acidic conditions - Ziyan Zhou; Hao Wu; Boming Fu; Zhe Wang; Ran Hong; Liuqing Huang; Xinyue Gu; Cheng Gu; Xin Jin (Journal of Hazardous Materials, 2023)

Particle high-speed self-rotation in cyclones with different diameters and application in catalyst deoiling - Qiong Li; Tingting Cheng; Qiqi Li; Junjie Liu; Yanan Liang; Jianping Li; Xia Jiang; Hualin Wang; Pengbo Fu (Journal of Cleaner Production, 2023)

Effective removal of cesium by ammonium molybdophosphate–polyethylene glycol magnetic nanoparticles - Chengyun Fu; Zhaomin Tan; Jianfeng Cheng; Jingli Xie; Xuezhi Dai; Yinyuan Du; Shan Zhu; Shaoqing Wang; Minhao Yan (Journal of Environmental Chemical Engineering, 2023)

The dual role of acetate additives among carbon materials functionalized and CH4/N2 separation - Shuohao Li; Shenguang Fu; Yuqing Gong; Yuanping Cheng; Liang Wang (Gas Science and Engineering, 2023)

Simultaneous elimination of N,N-dimethylhydrazine compounds and its oxidation by-product N-nitrosodimethylamine by UV-activated peroxymonosulfate process: Multiple-path mechanism validation and toxicity alteration - Linlu Shen; Hongyi Wang; Jing Kang; Jimin Shen; Pengwei Yan; Yingxu Gong; Jiaxu Zhang; Gang Fu; Shuyu Wang; Yizhen Cheng; Shengxin Zhao; Zhonglin Chen (Chemical Engineering Journal, 2023)

Regional specific tunable meniscus decellularized extracellular matrix (MdECM) reinforced bioink promotes anistropic meniscus regeneration - Zong Li; Wenqiang Yan; Fengyuan Zhao; Hongde Wang; Jin Cheng; Xiaoning Duan; Xin Fu; Jiying Zhang; Xiaoqing Hu; Yingfang Ao (Chemical Engineering Journal, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

New insight into efficient CH4/N2 separation based on Ni-decorated porous carbon functional composites - Shuohao Li; Shenguang Fu; Yuqing Gong; Liang Wang; Yuxiang Wu; Lei Wang; Yuanping Cheng (Fuel, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Push–pull plants in wheat intercropping system to manage Spodoptera frugiperda - Huan Liu; Yumeng Cheng; Qian Wang; Xiaobei Liu; Yu Fu; Yong Zhang; Julian Chen (Journal of Pest Science, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Developing and characterizing monoclonal antibodies of Guertu bandavirus nucleoprotein for developing methods of Guertu bandavirus and severe fever with thrombocytopenia syndrome virus detection - Jin Qian; Liyan Fu; Xiaoli Wu; Zhiying Wang; Hualin Wang; Yan Zeng; Guirong Cheng; Fei Deng; Shu Shen (Brazilian Journal of Microbiology, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Conversion and impact of dissolved organic matters in a heterogeneous catalytic peroxymonosulfate system for pollutant degradation - Yanshan Wang; Ning Li; Qinglong Fu; Zhanjun Cheng; Yingjin Song; Beibei Yan; Guanyi Chen; Li'an Hou; Shaobin Wang (Water Research, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Aberrant Histone Modification of TNFAIP3, TLR4, TNIP2, miR-146a, and miR-155 in Major Depressive Disorder - Chu-Chiao Tseng; Shao-Cheng Wang; Yi-Chien Yang; Hung-Chun Fu; Chen-Kai Chou; Hong-Yo Kang; Yi-Yung Hung (Molecular Neurobiology, 2023)

Effect of hexavalent chromium exposure on the reproductive status and biomarker responses of female Geloina erosa - Hongling Mu; Gongsi Wang; Bo Huang; Xiangchao Fu; Sui Cheng; Jiao Wen (Ecotoxicology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Spatial distribution, source, and ecological risk of polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecanes (HBCDs) in Jiaozhou Bay, China - Jie Fu; Haibo Zhang; Ruijing Li; Tengda Shi; Lisha Wang; Guanjie Cheng; Jiajin Huang; Shisheng Li; Hui Gao; Shuaichen Jin; Guangshui Na (Marine Pollution Bulletin, 2023)

Characteristics and sources of PM2.5-bound elements in Shanghai during autumn and winter of 2019: Insight into the development of pollution episodes - Yanan Chen; Xingnan Ye; Yinghui Yao; Zhixiao Lv; Zhenghang Fu; Cheng Huang; Ruoyan Wang; Jianmin Chen (Science of The Total Environment, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Utilization of constructed wetland technology in China's sponge city scheme under carbon neutral vision - Yamei Cai; Yaqian Zhao; Ting Wei; Wei Fu; Cheng Tang; Yujie Yuan; Qi Yin; Cong Wang (Journal of Water Process Engineering, 2023)

Arabinoxylan of varied structural features distinctively affects the functional and in vitro digestibility of wheat starch - Ji Kang; Zhi-Yan Huang-Fu; Xiaona Tian; Liting Cheng; Jixiang Zhang; Yan Liu; Yanfang Liu; Shujun Wang; Xinzhong Hu; Liang Zou; Qingbin Guo (Food Hydrocolloids, 2023)

Strong photo-thermal coupling effect boosts CO2 reduction into CH4 in a concentrated solar reactor - Lei Xu; Yuqi Ren; Yiwei Fu; Maochang Liu; Fengfan Zhu; Miao Cheng; Jiancheng Zhou; Wenshuai Chen; Ke Wang; Nan Wang; Naixu Li (Chemical Engineering Journal, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Miocene Moschidae (Mammalia, Ruminantia) from the Linxia Basin (China) connect Europe and Asia and show an early evolutionary diversity of a today monogeneric family - Manuela Aiglstorfer; Shi-Qi Wang; Jie Cheng; Luda Xing; Jiao Fu; Bastien Mennecart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Evaluation of modified bitumen properties using waste plastic pyrolysis wax as warm mix additives - Chuanqiang Li; Haobo Wang; Chaoliang Fu; Shaosong Shi; Guannan Li; Qizheng Liu; Dan Zhou; Lin Jiang; Ying Cheng (Journal of Cleaner Production, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Geochronology of a Paleoproterozoic metamorphic complex in the Shuangsheng area of Inner Mongolia: constraints on crustal evolution - Qian Cheng; Lu Lu; Yan Wang; Junyu Fu; Rongrong Guo; Hui Zhong; Xiaoping Yang; Jiyu Du (International Geology Review, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

Integrated volatilomic profiles and chemometrics provide new insights into the spatial distribution and aroma differences of volatile compounds in seven Toona sinensis cultivars - Cheng Wang; Chendan Fu; Yanfang Li; Yilan Zhang; Beibei Zhang; Jingfang Zhang (Food Chemistry, 2023)

One positive part of copper ion on biocatalysts: CNPs@Cu-Trypsin-assisted aqueous extraction technique for simultaneous exploration of edible insect oil and protein - Jin-Zheng Wang; Cheng-Kun Wu; Xin-Ying Wang; Yuan-Zhi Xu; Richard Ansah Herman; Sheng Sheng; Shuai You; Jun Wang; Fu-An Wu (Chemical Engineering Journal, 2023)

High-strength and recyclable pure chitosan films manufactured by an ionic liquid assisted roll-forming method - Shuang Sun; Jiaqi Zheng; Zijie Liu; Siluo Huang; Qikuan Cheng; Yue Fu; Weihao Cai; Dan Chen; Dong Wang; Huamin Zhou; Yunming Wang (Chemical Engineering Journal, 2023)

Silurian post-orogenic volcanic rocks of the South Kunlun Belt, NW China: links to the Proto- to Paleo-Tethyan tectonic transition - Jing Chen; Bing-Zhang Wang; Bin Li; Fu-Cheng Yu (International Geology Review, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Plow layer management during the fallow season can enhance the wheat productivity and resource utilization in a semi-arid region - Gang Zhao; Peng Wu; Fu Liu; Shangzhong Li; Jianjun Zhang; Yi Dang; Lei Wang; Shuying Wang; Wanli Cheng; Tie Cai; Tinglu Fan (Soil and Tillage Research, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

Dual polymer electrochromic sunglasses with black to anti-blue-ray conversion based on new anti-blue-ray transparent polymer - Haichang Fu; Yixiao Tang; Feng Zhan; Ling Zhang; Wang Zhan; Yujie Dong; Weijun Li; Cheng Zhang (Chemical Engineering Journal, 2023)

Vsig4+ resident single-Kupffer cells improve hepatic inflammation and fibrosis in NASH - Hui-Yi Li; Seng-Wang Fu; Jun-Cheng Wu; Zheng-Hong Li; Ming-Yi Xu (Inflammation Research, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Mesoporous molecularly imprinted nanoparticles with peptide mimics for the detection of phenolic compounds - Xingguo Liu; Xue Zhang; Zhendong Fu; Xianhui Cheng; Liping Wang; Lianghai Hu (Analytica Chimica Acta, 2023)

Secondary pollution of microplastic hetero-aggregates after chlorination: Released contaminants rarely re-adsorbed by the second-formed hetero-aggregates - Yan Jin; Minghui Li; Feiyong Chen; Lin Wang; Lijie Zhang; Zhigang Yang; Ning Wang; Jie Fu; Yang Yu; Xiaoxiang Cheng; Daoji Wu (Journal of Hazardous Materials, 2023)

Insights into multidimensional transport flux from vertical observation and numerical simulation in two cities in North China - Zhida Zhang; Xiaoqi Wang; Shuiyuan Cheng; Guiqian Tang; Yibin Fu (Journal of Environmental Sciences, 2023)

Integrated transcriptomic and volatilomic profiles to explore the potential mechanism of aroma formation in Toona sinensis - Cheng Wang; Beibei Zhang; Yanfang Li; Jing Hou; Chendan Fu; Zihui Wang; Jingfang Zhang (Food Research International, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

A bacterial cellulose-based separator with tunable pore size for lithium-ion batteries - Chen Cheng; Rendang Yang; Yang Wang; Danning Fu; Jie Sheng; Xiaohui Guo (Carbohydrate Polymers, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Occurrence, spatial distribution, and risk assessment of brominated flame retardants in farmland soils of typical provinces in China - Mabinty Sarah Tholley; Lartey Young George; Mengru Fu; Zhihua Qiao; Gehui Wang; Siyuan Ling; Cheng Peng; Wei Zhang; Chunmei Ye; Fang Liu; Jie Yang (Chemosphere, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Environmental fate of five brominated flame retardants co-exposure in a water-sediment-zebrafish microcosm system: Enrichment, removal, and metabolism mechanisms - Zhihua Qiao; Yawen Wang; Cong Lu; Siyuan Ling; Shanqi Zhou; Mengru Fu; Kailun Luo; Cheng Peng; Wei Zhang; Bingsheng Zhou (Journal of Cleaner Production, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Three-Dimensional Refined Modelling of Deep Structures by Using the Level Set Method: Application to the Zhaoping Detachment Fault, Jiaodong Peninsula, China - Jinli Wang; Xiancheng Mao; Cheng Peng; Jin Chen; Hao Deng; Zhankun Liu; Wensheng Wang; Zhengkai Fu; Chuntan Wang (Mathematical Geosciences, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

Geographical variation in the effect of ambient temperature on infectious diarrhea among children under 5 years - Hao Zheng; QingQing Wang; Jianguang Fu; Zhen Ding; Jian Cheng; Zhiwei Xu; Yan Xu; Yankai Xia (Environmental Research, 2023)

Data-driven, multi-moment fluid modeling of Landau damping - Wenjie Cheng; Haiyang Fu; Liang Wang; Chuanfei Dong; Yaqiu Jin; Mingle Jiang; Jiayu Ma; Yilan Qin; Kexin Liu (Computer Physics Communications, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

Molecularly understanding and regulating carrier injection behavior of ETL/perovskite towards high performance PeLEDs - Qungui Wang; Keli Wang; Cheng Yan; Xiankan Zeng; Xuehai Fu; Jingjing Cao; Shiyu Yang; Wen Li; Xiangrong Chen; Weiqing Yang (Chemical Engineering Journal, 2023)

Insight into a strategy to improve charge carrier migration in lead-free bismuth-based halide perovskite for efficient selective oxidation of thioanisole under visible light - Zihao Cui; Yaqiang Wu; Shuhui Zhang; Hui Fu; Guoqiang Chen; Zaizhu Lou; Xiaolei Liu; Qianqian Zhang; Zeyan Wang; Zhaoke Zheng; Hefeng Cheng; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

A microscale regulation strategy for strong, tough, and efficiently self-healing energetic adhesives - Jing Yang; Xin Zhou; Junqing Yang; Jiaoyang Chen; Zhe Sun; Yuhang Cheng; Lin Yang; Hui Wang; Guangpu Zhang; Jiajun Fu; Wei Jiang (Chemical Engineering Journal, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

The diversity and structure of diazotrophic communities in the rhizosphere of coastal saline plants is mainly affected by soil physicochemical factors but not host plant species - Yanjing Song; Lan Ma; Haiyang Zhang; Rao Fu; Xiaoyan Liang; Junlin Li; Jiajia Li; Meng Li; Yan Shan; Jieshan Cheng; Xiangyu Wang; Hongxia Zhang (Frontiers in Marine Science, 2022)
The diversity and community structure of rhizospheric microbes are largely affected by soil physicochemical properties and plant species. In this work, high throughput sequencing and quantitative real-time PCR targeting nifH gene were used to assess the abundance and diversity of diazotrophic community in the coastal saline soils of Yellow River Delta (YRD). We demonstrated that the copy number of nifH gene encoding the Fe protein subunit of the nitrogenase in the nitrogen fixation process was significantly affected by soil physiochemical factors, and the abundance of diazotrophs in the rhizospheric soil samples collected from different locations was positively related with soil physicochemical properties. Soil salinity ( P =0.003) and moisture ( P =0.003) were significantly co-varied with the OTU-based community composition of diazotrophs. Taxonomic analysis showed that most diazotrophs belonged to the Alphaproteobacteria , Gammaproteobacteria and Deltaproteobacteria . Linear discriminant analysis (LDA) effect size (LEfSe) and canonical correspondence analysis (CCA) showed that diazotrophic community structure significantly varied with soil salinity, moisture, pH and total nitrogen, carbon, sulphur and nitrite (NO 2 – N) content. Our findings provide direct evidence toward the understanding of different effects of soil physicochemical properties and host plant traits such as halophytes types, life span and cotyledon type, on the community composition of diazotrophic populations in the rhizosphere of plants grown in coastal saline soils.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Tannic acid attenuate AKT phosphorylation to inhibit UMUC3 bladder cancer cell proliferation - Ming-Cheng Chen; Selvaraj Annseles Rajula; V. Bharath Kumar; Chiung-Hung Hsu; Cecilia Hsuan Day; Ray-Jade Chen; Tso-Fu Wang; Vijaya Padma Viswanadha; Chi-Cheng Li; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Four sesquiterpenoids from the vegetable raw material Schisandra chinensis (Turcz.) Baill.: leaves and stems - Yong-Cheng Yang; Lu-Qi Liu; Kun-Jun Wang; Xue-Qing Zhang; San-Peng Fan; Xiao-Xu Gao; An-Hua Wang; Jing-Ming Jia; Chun-Wang Fu (Natural Product Research, 2022)

Hydrogen Sulfide Attenuates High-Fat Diet-Induced Obesity: Involvement of mTOR/IKK/NF-κB Signaling Pathway - Maofang Zhao; Yuan Cheng; Xiaoxuan Wang; Xiaoying Cui; Xiaojing Cheng; Qian Fu; Yilin Song; Peiquan Yu; Yi Liu; Yinghua Yu (Molecular Neurobiology, 2022)

Cessation of collisional tectonism and rapid crustal uplift recorded by 430–420 Ma igneous rocks in the South Kunlun belt, northwest China - Jing Chen; Bing-Zhang Wang; Fu-Cheng Yu; Jie Han; Wu-Fu Li (International Geology Review, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2022)

Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Xinyi Zhai; Xiaochong Shi; Haojin Cheng; Peng Yao; Bin Zhao; Lin Chen; Jiwen Liu; Lei Cao; Minxiao Wang; Lulu Fu; Xiao-Hua Zhang; Min Yu (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans , Sulfurovum , and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H 2 S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales , and Sulfurovum , which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.

Use of an Effective Variance Chemical Mass Balance Model for Source Apportionment of Metal Elements in a Polluted River - Pei-Yuan Hsieh; Chi-Chang Ho; Gen-Shuh Wang; Yuan-Cheng Hsu; Di-Wen Wang; Yu-Man Shang; Chang-Fu Wu (Environmental Processes, 2022)

Food irradiation: a promising technology to produce hypoallergenic food with high quality - Xiaowen Pi; Yili Yang; Yuxue Sun; Xibo Wang; Yin Wan; Guiming Fu; Xin Li; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Biomechanical Analysis of the External Fixation in a Lumbar Fracture Model: A Finite Element Study - Yijia Liao; Yiguo Yan; Yu Kang; Wenjun Wang; Xizheng Song; Wen Peng; Haibin Fu; Huarong Chen; Cheng Wang (Journal of Medical and Biological Engineering, 2022)
Purpose This study aimed to investigate the biomechanical characteristics of the external spinal fixation for treating lumbar fracture through finite element analysis (FEA) and provide a theoretical basis for its further application. Methods Two different models of L3 fracture fixed with the external spinal fixation and the internal fixation system respectively were constructed. The ROM, maximum stresses at L3, and the screws of the two models were measured under load control. Subsequently, the applied torque, the maximum stressed at L3, L1/2, L2/3, L3/4, L4/5 discs and the screws were analyzed under displacement control. Results Under load control, the external fixation model reserved more ROM than the internal fixation model (40.4–48.0% vs 30.5–41.0%). Compared to the internal fixation model, the maximum stresses at L3 and screws in the external fixation model were increased. Under displacement control, the external fixation model required fewer moments (N·mm) than the internal fixation model (flexion: 7500 vs 12,294; extension: 7500 vs 9027). Further, the maximum stresses at L3 and the screws in the external fixation model were greater than those of the internal fixation model, while the maximum stresses at the upper and lower adjacent discs of fixed segments were less than the internal fixation model. Conclusion Compared to the internal fixation system, the external fixation has a better stress distribution with the greater overall mobility. It theoretically reduces the stress concentration of the adjacent discs and the stress shielding of the fractured vertebral body.

Alteromonas oceanisediminis sp. nov., isolated from deep-sea sediment - Xiao-Yu Zhang; Zhen Wang; Jun-Hui Cheng; Hui-Hui Fu; Yu-Zhong Zhang; Xiu-Lan Chen; Xi-Ying Zhang; Xiao-Yan Song; Yu-Qiang Zhang; Fei Xu (Archives of Microbiology, 2022)

Correction to: Chitosan‑based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu‑Wei Huang; Fang‑Ching Yeh; You‑Ren Ji; Ying‑Fu Su; Ying‑shih Su; Ming‑Hsien Chiang; Shian‑Chiuan Tzeng; Chien‑Yao Fu; Aristine Cheng; Yung‑Chih Wang; Yi‑Tzu Lee (Drug Delivery and Translational Research, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

An autopolyploid-suitable polyBSA-seq strategy for screening candidate genetic markers linked to leaf blight resistance in sugarcane - Zhoutao Wang; Hui Ren; Chao Pang; Guilong Lu; Fu Xu; Wei Cheng; Youxiong Que; Liping Xu (Theoretical and Applied Genetics, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Association between serum folate levels and blood concentrations of cadmium and lead in US adults - Zuxiang Wu; Huan Hu; Chenxi Wang; Ji Wu; Yurong Xiong; Yang Fu; Xiaoshu Cheng; Hai Su; Ping Li (Environmental Science and Pollution Research, 2022)

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Discriminating hydrocarbon generation potential of coaly source rocks and their contribution: a case study from the Upper Paleozoic of Bohai Bay Basin, China - Jinjun Xu; Da Lou; Qiang Jin; Lixin Fu; Fuqi Cheng; Shuhui Zhou; Xiuhong Wang; Chao Liang; Fulai Li (Frontiers of Earth Science, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Dietary protein-phenolic interactions: characterization, biochemical-physiological consequences, and potential food applications - Qiaozhi Zhang; Zhouzhou Cheng; Yanbo Wang; Linglin Fu (Critical Reviews in Food Science and Nutrition, 2021)

YTHDF1 promotes NLRP3 translation to induce intestinal epithelial cell inflammatory injury during endotoxic shock - Xin Zong; Xiao Xiao; Fu Jie; Yuanzhi Cheng; Mingliang Jin; Yulong Yin; Yizhen Wang (Science China Life Sciences, 2021)

Comparative physiological and proteomic analyses of mangrove plant Kandelia obovata under cold stress - Jiao Fei; You-Shao Wang; Hao Cheng; Fu-Lin Sun; Cui-Ci Sun (Ecotoxicology, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

BnA1.CER4 and BnC1.CER4 are redundantly involved in branched primary alcohols in the cuticle wax of Brassica napus - Jie Liu; Lixia Zhu; Benqi Wang; Huadong Wang; Imran khan; Shuqin Zhang; Jing Wen; Chaozhi Ma; Cheng Dai; Jinxing Tu; Jinxiong Shen; Bin Yi; et al. (Theoretical and Applied Genetics, 2021)

HDAC inhibitors improve CRISPR-mediated HDR editing efficiency in iPSCs - Jian-Ping Zhang; Zhi-Xue Yang; Feng Zhang; Ya-Wen Fu; Xin-Yue Dai; Wei Wen; Beldon Zhang; Hannah Choi; Wanqiu Chen; Meredith Brown; David Baylink; Lei Zhang; et al. (Science China Life Sciences, 2021)

A high-resolution typical pollution source emission inventory and pollution source changes during the COVID-19 lockdown in a megacity, China - Xue Hu; Qizhen Liu; Qingyan Fu; Hao Xu; Yin Shen; Dengguo Liu; Yue Wang; Haohao Jia; Jinping Cheng (Environmental Science and Pollution Research, 2021)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2021)
Summary Fusarium graminearum is an important worldwide pathogen that causes Fusarium head blight in wheat, barley, maize and other grains. LncRNAs play important roles in many biological processes, but little is known about their functions and mechanisms in filamentous fungi. Here, we report that a natural antisense RNA, GzmetE‐AS , is transcribed from the opposite strand of GzmetE . GzmetE encodes a homoserine O ‐acetyltransferase, which is important for sexual development and plant infection. The expression of GzmetE‐AS was increased significantly during the conidiation stage, while GzmetE was upregulated in the late stage of sexual reproduction. Overexpression of GzmetE‐AS inhibited the transcription of GzmetE . In contrast, the expression of GzmetE was significantly increased in GzmetE‐AS transcription termination strain GzmetE‐AS ‐T. Furthermore, GzmetE‐AS ‐T produced more perithecia and facilitated the ascospore discharge, resembling the phenotype of GzmetE overexpressing strains. However, overexpression of GzmetE‐AS in ∆dcl1/2 strain cannot inhibit the expression of GzmetE , and the GzmetE nat‐siRNA is also significantly reduced in ∆dcl1/2 mutant. Taken together, we have identified a novel antisense lncRNA GzmetE‐AS , which is involved in asexual and sexual reproduction by regulating its antisense gene GzmetE through RNAi pathway. Our findings reveal that the lncRNA plays critical roles in the development of F . graminearum .

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu-Wei Huang; Fang-Ching Yeh; You-Ren Ji; Ying-Fu Su; Ying-shih Su; Ming-Hsien Chiang; Shian-Chiuan Tzeng; Chien-Yao Fu; Aristine Cheng; Yung-Chih Wang; Yi-Tzu Lee (Drug Delivery and Translational Research, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Estimations of Land Surface Characteristic Parameters and Turbulent Heat Fluxes over the Tibetan Plateau Based on FY-4A/AGRI Data - Nan Ge; Lei Zhong; Yaoming Ma; Yunfei Fu; Mijun Zou; Meilin Cheng; Xian Wang; Ziyu Huang (Advances in Atmospheric Sciences, 2021)

Temperature-induced changes in the proteome of Pseudomonas aeruginosa during petroleum hydrocarbon degradation - Jun-Di Wang; Cheng-Tun Qu; Shao-Fu Song (Archives of Microbiology, 2021)

A mitochondria-localized pentatricopeptide repeat protein is required to restore hau cytoplasmic male sterility in Brassica napus - Huadong Wang; Qing Xiao; Chao Wei; Hui Chen; Xiaohan Chen; Cheng Dai; Jing Wen; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen; Bin Yi (Theoretical and Applied Genetics, 2021)

A female carrier of a novel DMD mutation with slightly skewed X-chromosome inactivation shows a suspected case of Becker muscular dystrophy in a Chinese family - Jianfan Chen; Hui Zheng; Zhongju Wang; Jian Wang; Fei He; Cheng Zhang; Fu Xiong (Molecular Genetics and Genomics, 2021)

Pollution characteristics and risk assessment of surface sediments in the urban lakes - Na Cheng; Laisheng Liu; Zelin Hou; Jiapeng Wu; Qiwen Wang; Yicheng Fu (Environmental Science and Pollution Research, 2021)

Niacin stimulates EPH4EV mammary epithelial cell proliferation and mammary gland development in pubertal mice through activation of AKT/mTOR and ERK1/2 signaling pathways - Yu Cao; Yan Zhang; Lijun Ma; Jiaxin Wang; Wenjin Guo; Ji Cheng; Guiqiu Hu; Shoupeng Fu; Juxiong Liu (Cell and Tissue Research, 2021)

Structure of SARS-CoV-2 main protease in the apo state - Xuelan Zhou; Fanglin Zhong; Cheng Lin; Xiaohui Hu; Yan Zhang; Bing Xiong; Xiushan Yin; Jinheng Fu; Wei He; Jingjing Duan; Yang Fu; Huan Zhou; et al. (Science China Life Sciences, 2021)

Drivers of phenology shifts and their effect on productivity in northern grassland of China during 1984–2017—evidence from long-term observational data - Lingling Xu; Xianzhou Zhang; Yongli Wang; Yang Fu; Hao Yan; Shuan Qian; Lu Cheng (International Journal of Biometeorology, 2021)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Lactobacillus rhamnosus JYLR-005 Prevents Thiram-Induced Tibial Dyschondroplasia by Enhancing Bone-Related Growth Performance in Chickens - Fang Liu; Anan Kong; Pengfei Fu; Qin-qin Cao; Kun-sheng Tao; Di-yi Liu; Xue-bing Wang; Zong-xi Tong; Mujeeb Ur Rehman; Shu-cheng Huang (Probiotics and Antimicrobial Proteins, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Correction to: A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2021)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

PKCβ/NF-κB pathway in diabetic atrial remodeling - Haili Wang; Yuanyuan Xu; Aiqing Xu; Xinghua Wang; Lijun Cheng; Sharen Lee; Gary Tse; Guangping Li; Tong Liu; Huaying Fu (Journal of Physiology and Biochemistry, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Silencing of long non-coding RNA CRNDE promotes autophagy and alleviates neonatal hypoxic-ischemic brain damage in rats - Chun-Hua Fu; Fang-Fang Lai; Sai Chen; Cai-Xia Yan; Bing-Hong Zhang; Cheng-Zhi Fang; Gao-Hua Wang (Molecular and Cellular Biochemistry, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Lacustrine record from the eastern Tibetan Plateau associated with Asian summer monsoon changes over the past ~ 6 ka and its links with solar and ENSO activity - Guodong Ming; Weijian Zhou; Peng Cheng; Hong Wang; Feng Xian; Yunchong Fu; Shugang Wu; Hua Du (Climate Dynamics, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Two-Year Observation of Fossil Fuel Carbon Dioxide Spatial Distribution in Xi’an City - Xiaohu Xiong; Weijian Zhou; Shugang Wu; Peng Cheng; Hua Du; Yaoyao Hou; Zhenchuan Niu; Peng Wang; Xuefeng Lu; Yunchong Fu (Advances in Atmospheric Sciences, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Genome optimization for improvement of maize breeding - Shuqin Jiang; Qian Cheng; Jun Yan; Ran Fu; Xiangfeng Wang (Theoretical and Applied Genetics, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

GPS satellite inter-frequency clock bias estimation using triple-frequency raw observations - Lei Fan; Chuang Shi; Min Li; Cheng Wang; Fu Zheng; Guifei Jing; Jun Zhang (Journal of Geodesy, 2019)

Risk Assessment of Crop Production Amid Climate Change Based on the Principle of Maximum Entropy: A Case Study of Winter Wheat Production on the North China Plain - Zhan-biao Wang; Cheng-sheng Meng; Jing Chen; Fu Chen (International Journal of Plant Production, 2019)

Quality control of online monitoring data of air pollutants using artificial neural networks - Ziyu Wang; Jingjing Feng; Qingyan Fu; Song Gao; Xiaojia Chen; Jinping Cheng (Air Quality, Atmosphere & Health, 2019)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

The Ribosomal Protein RPLP0 Mediates PLAAT4-induced Cell Cycle Arrest and Cell Apoptosis - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Ming-Cheng Lee; Yi-Ying Lin; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2019)

Modelling spatial variation in the treatment costs of non-point source pollution in mountainous regions of southwest China - Ju Liu; Bin Fu; Cheng-hu Zhang; Yu-kuan Wang (Journal of Mountain Science, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Late Cretaceous magmatism and porphyry Mo–Cu polymetallic mineralization in the Tongchanggou Intrusion, Geza Arc, Southwestern China - Xue-long Liu; Jian-hang Chen; Wen-chang Li; Na Zhang; Shuai-shuai Wang; Chang-zhen Zhang; Ying Luo; Zhen-huan Li; Fu-cheng Yang (Arabian Journal of Geosciences, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Pine needles as biomonitors of polybrominated diphenyl ethers and emerging flame retardants in the atmosphere of Shanghai, China: occurrence, spatial distributions, and possible sources - Hao-Hao Jia; Xue-Tong Wang; Hang-Xin Cheng; Ying Zhou; Rui Fu (Environmental Science and Pollution Research, 2019)

Characterization of a novel RNA virus from the phytopathogenic fungus Leptosphaeria biglobosa related to members of the genus Mitovirus - Yong Wang; Zhiyong Xu; Jiasen Cheng; Yanping Fu; Daohong Jiang; Jiatao Xie (Archives of Virology, 2019)

Application of computed tomography in the analysis of glass beads unearthed in Shanpula cemetery (Khotan), Xinjiang Uyghur Autonomous Region - Qian Cheng; Xueyan Zhang; Jinlong Guo; Bo Wang; Yong Lei; Guangzhao Zhou; Ya’nan Fu (Archaeological and Anthropological Sciences, 2019)

Cerebrospinal fluid otorrhea secondary to congenital inner ear dysplasia: diagnosis and management of 18 cases - Bing Wang; Wen-jia Dai; Xiao-ting Cheng; Wen-yi Liuyang; Ya-sheng Yuan; Chun-fu Dai; Yi-lai Shu; Bing Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

Investigate the impact of local iron–steel industrial emission on atmospheric mercury concentration in Yangtze River Delta, China - Deming Han; Qingyan Fu; Song Gao; Xufeng Zhang; Jingjing Feng; Xiaolin Chen; Xiqian Huang; Haoxiang Liao; Jinping Cheng; Wenhua Wang (Environmental Science and Pollution Research, 2019)

Surface mulching and a sandy soil interlayer suppress upward enrichment of salt ions in salt-contaminated field - Jianyong Wang; Huiming Liu; Shaoming Wang; Yingxia Liu; Zhengguo Cheng; Guangqiang Fu; Fei Mo; Youcai Xiong (Journal of Soils and Sediments, 2019)

ATMT transformation efficiencies with native promoters in Botryosphaeria kuwatsukai causing ring rot disease in pear - Xueying Gu; Jiamin Zhao; Hongkai Wang; Fu-Cheng Lin; Qingyuan Guo; Neeraj Shrivastava; Rajesh Jeewon (World Journal of Microbiology and Biotechnology, 2018)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

Estimation of groundwater discharge and associated chemical fluxes into Poyang Lake, China: approaches using stable isotopes (δD and δ18O) and radon - Fu Liao; Guangcai Wang; Zheming Shi; Guoqiang Cheng; Qingmin Kong; Wenqing Mu; Liang Guo (Hydrogeology Journal, 2018)

Programmed cell death in wheat (Triticum aestivum L.) endosperm cells is affected by drought stress - Chao Li; Cheng Li; Bingbing Wang; Runqi Zhang; Kaiyong Fu; William J. Gale; Chunyan Li (Protoplasma, 2018)

Three-dimensional analyses of the sliding surface distribution in the Huangtupo No. 1 riverside sliding mass in the Three Gorges Reservoir area of China - Jinge Wang; Aijun Su; Qingbing Liu; Wei Xiang; Hsin-Fu Yeh; Chengren Xiong; Zongxing Zou; Cheng Zhong; Junqi Liu; Shen Cao (Landslides, 2018)

Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms - Si Yu; Lijiao Wang; Zhixing Cao; Daoyin Gong; Qianyi Liang; Hanting Chen; Huizhu Fu; Wenwen Wang; Xue Tang; Zihao Xie; Yang He; Cheng Peng; et al. (Natural Product Research, 2018)

Crystal structure of Psb27 from Arabidopsis thaliana determined at a resolution of 1.85 Å - Cheng Xingxing; Liu Jiuyang; Zhang Huan; Li Fudong; Zhang Shuya; Xu Min; Ruan Ke; Wang Yuhua; Fu Aigen (Photosynthesis Research, 2018)

Seismic responses of the steel-strip reinforced soil retaining wall with full-height rigid facing from shaking table test - Li-cong Cao; Xiao Fu; Zhi-jia Wang; Yong-yi Zhou; Fei-cheng Liu; Jian-jing Zhang (Journal of Mountain Science, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Structural characterisation of a water-soluble polysaccharide from tissue-cultured Dendrobium huoshanense C.Z. Tang et S.J. Cheng - Hua-Yang Si; Nai-Fu Chen; Nai-Dong Chen; Cheng Huang; Jun Li; Hui Wang (Natural Product Research, 2018)

A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2018)

Flocculation of coal washing wastewater using polysaccharide produced by Paenibacillus mucilaginosus WL412 - Haiyang Xu; Jing Li; Renjie Fu; Rui Cheng; Shiming Wang; Jianfa Zhang (Environmental Science and Pollution Research, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Effects of reduced pH and elevated pCO 2 on sperm motility and fertilisation success in blood clam, Tegillarca granosa - Wei Shi; Xinguo Zhao; Yu Han; Cheng Guo; Saixi Liu; Wenhao Su; Yichen Wang; Shanjie Zha; Xueliang Chai; Wandong Fu; Huicheng Yang; Guangxu Liu (New Zealand Journal of Marine and Freshwater Research, 2017)
Although it has been shown that ocean acidification generally has a negative impact on fertilisation success of broadcast spawning marine organisms, whether induced fertilisation success reduction is a consequence of elevated p CO 2 or decreased pH remains unclear. Therefore, the impacts of HCl‐ and CO 2 ‐induced acidified seawater on sperm motility and gametes fertilisation capability of a broadcast spawning bivalve species, Tegillarca granosa were investigated in the present study. The results showed that the fertilisation capability of both gametes was significantly reduced in either HCl‐ or CO 2 ‐acidified seawater. In addition, significant impacts on sperm motility were observed in the group exposed to CO 2 ‐acidified seawater, suggesting that this parameter is sensitive to p CO 2 instead of solely pH value. The differences between the two seawater acidification manipulating methods may be due to the intrinsic difference in diffusion capability of CO 2 and protons.

Field testing of the surface electromagnetic prospecting system - Qing-Yun Di; Chang-Min Fu; Zhi-Guo An; Cheng Xu; Ya-Lu Wang; Zhong-Xing Wang (Applied Geophysics, 2017)

Detection of exercise periodic breathing using thermal flowmeter in patients with heart failure - Tieh-Cheng Fu; Wen-Chen Lin; Jong-Shyan Wang; Chao-Hung Wang; Chun-Tien Chang; Cheng-Lun Tsai; Yun-Shien Lee; Kang-Ping Lin (Medical & Biological Engineering & Computing, 2017)

Genotypic-dependent effects of N fertilizer, glutathione, silicon, zinc, and selenium on proteomic profiles, amino acid contents, and quality of rice genotypes with contrasting grain Cd accumulation - Fangbin Cao; Manman Fu; Runfeng Wang; Wangda Cheng; Guoping Zhang; Feibo Wu (Functional & Integrative Genomics, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Mapping the hotspots and coldspots of ecosystem services in conservation priority setting - Yingjie Li; Liwei Zhang; Junping Yan; Pengtao Wang; Ningke Hu; Wei Cheng; Bojie Fu (Journal of Geographical Sciences, 2017)

Ginsenoside Rg1 promotes neural differentiation of mouse adipose-derived stem cells via the miRNA-124 signaling pathway - Juan Dong; Guo Zhu; Tian-cheng Wang; Fu-shan Shi (Journal of Zhejiang University-SCIENCE B, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Platelet receptor Gene (P2Y12, P2Y1) and platelet glycoprotein Gene (GPIIIa) polymorphisms are associated with antiplatelet drug responsiveness and clinical outcomes after acute minor ischemic stroke - Xingyang Yi; Qiang Zhou; Chun Wang; Jing Lin; Ping Liu; Cheng Fu (European Journal of Clinical Pharmacology, 2017)

Using a global reference sample set and a cropland map for area estimation in China - Le Yu; XueCao Li; CongCong Li; YuanYuan Zhao; ZhenGuo Niu; HuaBing Huang; Jie Wang; YuQi Cheng; Hui Lu; YaLi Si; ChaoQing Yu; HaoHuan Fu; et al. (Science China Earth Sciences, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Tornado hazards on June 23 in Jiangsu Province, China: preliminary investigation and analysis - Hai-Min Lyu; Guo-Fu Wang; Wen-Chieh Cheng; Shui-Long Shen (Natural Hazards, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

New data and interpretations of the shallow and deep deformation of Huangtupo No. 1 riverside sliding mass during seasonal rainfall and water level fluctuation - Jinge Wang; Aijun Su; Wei Xiang; Hsin-Fu Yeh; Chengren Xiong; Zongxing Zou; Cheng Zhong; Qingbing Liu (Landslides, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The association between diurnal temperature range and childhood bacillary dysentery - Li-ying Wen; Ke-fu Zhao; Jian Cheng; Xu Wang; Hui-hui Yang; Ke-sheng Li; Zhi-wei Xu; Hong Su (International Journal of Biometeorology, 2016)

The spatial distribution of fossil fuel CO2 traced by Δ14C in the leaves of gingko (Ginkgo biloba L.) in Beijing City, China - Zhenchuan Niu; Weijian Zhou; Xiaoshan Zhang; Sen Wang; Dongxia Zhang; Xuefeng Lu; Peng Cheng; Shugang Wu; Xiaohu Xiong; Hua Du; Yunchong Fu (Environmental Science and Pollution Research, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Retraction Note to: Relationships of LDLR genetic polymorphisms with cerebral infarction: a meta-analysis - Hai-Cheng Yan; Wei Wang; Chang-Wu Dou; Fu-Ming Tian; Song-Tao Qi (Molecular Biology Reports, 2015)

Genomic organization of a novel victorivirus from the rice blast fungus Magnaporthe oryzae - Lihua Tang; Yanping Hu; Lijiang Liu; Songsong Wu; Jiatao Xie; Jiasen Cheng; Yanping Fu; Guoming Zhang; Juntao Ma; Yongli Wang; Liyan Zhang (Archives of Virology, 2015)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Spatial and vertical distribution of bacterial community in the northern South China Sea - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Hao Cheng (Ecotoxicology, 2015)

Recent changes in precipitation extremes in the Heihe River basin, Northwest China - Aifang Cheng; Qi Feng; Guobin Fu; Jiankai Zhang; Zongxing Li; Meng Hu; Gang Wang (Advances in Atmospheric Sciences, 2015)

Reflux characteristics of 113 GERD patients with abnormal 24-h multichannel intraluminal impedance-pH tests - Yuan-yuan Nian; Cheng Feng; Fu-chun Jing; Xue-qin Wang; Jun Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Effects of Spatial-Temporal Imperviousness on Hydrological Responses of Various Areas in an Urbanized Watershed - Yu-ming Wang; Yu-ji Li; Shin-jen Cheng; Fu-ti Yang; Yin-ta Chen (Water Resources Management, 2015)

Production of transgenic beef cattle rich in n-3 PUFAs by somatic cell nuclear transfer - Gong Cheng; Changzhen Fu; Hong Wang; C. Adoligbe; Shengjuan Wei; Shijun Li; Bijie Jiang; Hongbao Wang; Linsen Zan (Biotechnology Letters, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Pseudomonas songnenensis sp. nov., isolated from saline and alkaline soils in Songnen Plain, China - Lei Zhang; Yuanyuan Pan; Kaibiao Wang; Xiaoxia Zhang; Shuang Zhang; Xiaowei Fu; Cheng Zhang; Juquan Jiang (Antonie van Leeuwenhoek, 2015)

Integrated risk assessment method of waterlog disaster in Huaihe River Basin of China - Ju-Liang Jin; Juan Fu; Yi-Ming Wei; Shang-Ming Jiang; Yu-Liang Zhou; Li Liu; You-Zhen Wang; Cheng-Guo Wu (Natural Hazards, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

The Clinical Study of the Optimalization of Surgical Treatment and the Traditional Chinese Medicine Intervention on Palmar Hyperhidrosis - Yong Yang; Zhikun Yan; Xiaoqing Fu; Liwen Dong; Linhai Xu; Jun Wang; Genmiao Cheng (Cell Biochemistry and Biophysics, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

RETRACTED ARTICLE: Relationships of LDLR genetic polymorphisms with cerebral infarction: a meta-analysis - Hai-Cheng Yan; Wei Wang; Chang-Wu Dou; Fu-Ming Tian; Song-Tao Qi (Molecular Biology Reports, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Research on global change scientific satellites - HuaDong Guo; WenXue Fu; XinWu Li; Pei Chen; Guang Liu; Zhen Li; Cheng Wang; Qing Dong; LiPing Lei; LinYan Bai; QingJie Liu (Science China Earth Sciences, 2014)

Sequence analysis of bovine C/EBPδ gene and its adipogenic effects on fibroblasts - Hong Wang; Gong Cheng; Changzhen Fu; Hongbao Wang; Wucai Yang; Hongcheng Wang; Linsen Zan (Molecular Biology Reports, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Using RPC Block Adjustment models for the accuracy of environmental research, cartography and geomarketing: a new concept of cartography - Fu-Yung Kuan; Yen-Ping Ho; Ruei-Yuan Wang; Cheng-Wu Chen (Stochastic Environmental Research and Risk Assessment, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Tetracyclic spirooxindole blockers of hNaV1.7: activity in vitro and in CFA-induced inflammatory pain model - Sultan Chowdhury; Shifeng Liu; Jay A. Cadieux; Tom Hsieh; Mikhail Chafeev; Shaoyi Sun; Qi Jia; Jianyu Sun; Mark Wood; Jonathan Langille; Serguei Sviridov; Jianmin Fu; et al. (Medicinal Chemistry Research, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The polymorphisms of LYRM1 gene and their association with body measurement and ultrasound traits of Qinchuan cattle - Yaokun Li; Jianbin Gao; Ning Yang; Changzhen Fu; Gong Cheng; Hongbao Wang; Linsen Zan (Molecular Biology Reports, 2013)

Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

A novel lignan glycoside with antioxidant activity from Tinospora sagittata var. yunnanensis - Xiang-Zhong Huang; Chun-Mei Cheng; Yun Dai; Guang-Miao Fu; Jun-Ming Guo; Hui Liang; Chao Wang (Natural Product Research, 2012)

Analysis of QTL for yield-related traits in cassava using an F1 population from non-inbred parents - Xin Chen; Yuhua Fu; Zhiqiang Xia; Li Jie; Haiyan Wang; Cheng Lu; Wenquan Wang (Euphytica, 2012)

Association between MTHFR C677T polymorphism and osteonecrosis of the femoral head: a meta-analysis - Xi-fu Shang; Hong Su; Wei-wei Chang; Chen-cheng Wang; Qin Han; Zhi-wei Xu (Molecular Biology Reports, 2012)

Basin-scale groundwater response to precipitation variation and anthropogenic pumping in Chih-Ben watershed, Taiwan - Kuo-Chin Hsu; Hsin-Fu Yeh; You-Cheng Chen; Cheng-Haw Lee; Chung-Ho Wang; Feng-Sheng Chiu (Hydrogeology Journal, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Microcalorimetric study of the effect of Benzoinum and Styrax on the growth of Escherichia coli - Jian Wang; Danhong Cheng; Nan Zeng; Houlin Xia; Yong Fu; Dan Yan; Yanling Zhao; Xiaohe Xiao (Natural Product Research, 2011)

Constructing a Genetic Linkage Map Using an F1 Population of Non-inbred Parents in Cassava (Manihot esculenta Crantz) - Xin Chen; Zhiqiang Xia; Yuhua Fu; Cheng Lu; Wenquan Wang (Plant Molecular Biology Reporter, 2010)

Determination of flavonoid compounds from Saussurea involucrata by liquid chromatography electrospray ionisation mass spectrometry - Y.J. Xu; D.X. Zhao; C.X. Fu; L.Q. Cheng; N.F. Wang; L.J. Han; F.S. Ma (Natural Product Research, 2009)

Protein phosphatase 1A (PPM1A) is involved in human cytotrophoblast cell invasion and migration - Baohua Zhang; Zhi Zhou; Haiyan Lin; Xiaoyin Lv; Jiejun Fu; Ping Lin; Cheng Zhu; Hongmei Wang (Histochemistry and Cell Biology, 2009)

Ligand-induced nuclear translocation of S1P1 receptors mediates Cyr61 and CTGF transcription in endothelial cells - Rosendo Estrada; Lichun Wang; Venkatakrishna R. Jala; Jen-Fu Lee; Cheng-Yon Lin; Robert D. Gray; Bodduluri Haribabu; Menq-Jer Lee (Histochemistry and Cell Biology, 2009)

Identification, expression and tissue distribution of a renalase homologue from mouse - Jian Wang; Shaoling Qi; Wei Cheng; Li Li; Fu Wang; Ying-Zi Li; Shu-Ping Zhang (Molecular Biology Reports, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

New and rare lignicolous hyphomycetes from Zhejiang Province, China - Mongkol Wongsawas; Hong-kai Wang; Kevin D. Hyde; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Fungal diversity on fallen leaves of Ficus in northern Thailand - Hong-kai Wang; Kevin D. Hyde; Kasem Soytong; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Treatment with proteasome inhibitor bortezomib enhances antigen-specific CD8+ T-cell-mediated antitumor immunity induced by DNA vaccination - Chih-Wen Tseng; Archana Monie; Chao-Yi Wu; Bruce Huang; Mei-Cheng Wang; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2008)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Essential oil of Actinidia macrosperma, a catnip response kiwi endemic to China - Yun-peng Zhao; Xiao-yun Wang; Zhi-can Wang; Yin Lu; Cheng-xin Fu; Shao-yuan Chen (Journal of Zhejiang University-SCIENCE B, 2006)

Immunohistochemical Detection of Apoptotic Proteins, p53/Bax and JNK/FasL Cascade, in the Lung of Rats Exposed to Cigarette Smoke - Cheng-Hsun Wu; Hui-Hsuan Lin; Fu-Pin Yan; Cheng-Hua Wu; Chau-Jong Wang (Archives of Toxicology, 2006)

Promoter trapping in Magnaporthe grisea - Xiao-hong Liu; Jian-ping Lu; Jiao-yu Wang; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2006)